Carbon black composition to improve aesthetic and mechanical properties of elastomer compounds
Patent Information
- Application Number
- JP2024196960
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-01-12
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-19
AI Technical Summary
【0052】 本発明の別の態様は、(a)30.5~146.75mg/gの範囲内のヨウ素吸着価、31.5~139.9m2/gの範囲内の窒素表面積(NSA)、73~121.4ml/100gの範囲内の吸油価(OAN)を有する、少なくとも1つの第1のカーボンブラック;および(b)162.0~292.0mg/gの範囲内のヨウ素吸着価、160~294.0m2/gの範囲内の窒素表面積(NSA)、50~120ml/100gの範囲内の吸油価(OAN)を有する少なくとも1つの第2のカーボンブラックと、を組み合わせたカーボンブラック組成物と、ゴム化合物と、を含み、 前記カーボンブラック組成物中の前記第2のカーボンブラックは、0重量%~50重量%の範囲内で変動し、 前記カーボンブラック組成物は、半値全幅で示される凝集体サイズの分布の幅を有し、前記幅は、前記範囲内における、前記カーボンブラック組成物内の前記第2のカーボンブラックの重量%の増加とともに向上し、 前記幅は、前記第1のカーボンブラックがN339の場合、63nm~88nmの範囲内であり、前記第1のカーボンブラックがN134の場合、55nm~58nmの範囲内であり、前記第1のカーボンブラックがN660の場合、153nm~157nmの範囲内であり、 前記カーボンブラック組成物の質量加重平均凝集体サイズDWと数加重平均凝集体サイズDNの比は、前記第1のカーボンブラックがN339の場合、1.4~2の範囲内であり、前記第1のカーボンブラックがN134の場合、1.4~1.52の範囲内であり、前記第1のカーボンブラックがN660の場合、1.57~4.02の範囲内であり、 前記幅と前記分布のモードとの比によって定義される、前記分布の曲線の広がりの大きさは、前記第1のカーボンブラックがN339の場合、0.63~0.9の範囲内であり、前記第1のカーボンブラックがN134の場合、0.77~0.88の範囲内であり、前記第1のカーボンブラックがN660の場合、0.83~0.88の範囲内である、 前記エラストマー化合物を提供することに関する。
Smart Images

Figure 2025024063000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to novel carbon black compositions having a synergistically improved distribution of aggregate sizes ΔD50 which, when incorporated into natural or synthetic rubber elastomeric compounds or selected mixtures thereof, exhibit L * The present invention improves the aesthetic and color properties of elastomeric compounds such as value, and improves the mechanical properties such as tensile strength, elongation at break, tear strength, and break growth. [Background technology]
[0002] The appearance or aesthetics of tire body sections, sidewalls, various molded and extruded elastomeric articles gradually deteriorates over time or with continued use, mainly due to the incorporation of carbon black grades that exhibit inherently weak color performance, and also due to slow surface blooming of various chemical additives incorporated into elastomeric compounds during compounding to protect the elastomeric compounds from short and long term aging, facilitate processing, etc. During continued use, the initiation of surface cracks and the gradual growth of surface cracks also play an important role in the loss of aesthetics of elastomeric articles.
[0003] Beyond appearance or aesthetics, tire body and sidewall elastomeric compounds, molded elastomeric articles, extruded elastomeric articles must meet certain performance requirements, such as mechanical properties such as tensile strength, elongation at break, modulus, cut / chipping resistance, abrasion resistance, cut initiation, cut growth, tear resistance and dynamic mechanical properties.
[0004] The stringency of these performance requirements varies widely depending on the type of tire, the type of use to which the tire is subjected, the application of molded and extruded elastomeric articles, and the like.
[0005] Generally, carbon black is incorporated into elastomeric compounds in tire body sections, sidewalls, molded articles and extruded articles to achieve performance requirements such as mechanical properties of the articles, such as tensile strength, elongation at break, modulus, cut / chipping resistance, abrasion resistance, cut initiation, cut growth, tear resistance and dynamic mechanical properties.
[0006] In the rubber industry, two types of carbon black are commonly used to reinforce rubber. Hard grade carbon black imparts high abrasion resistance to the rubber being formulated and is commonly used to make vehicle tire treads. Soft grade carbon black is commonly used to reinforce rubber that is expected to encounter heavy flexing. Hard grade carbon blacks are generally classified as N100, N200, or N300 series. Soft grade carbon blacks are generally classified as N500, N600, and N700 series.
[0007] Additionally, a range of carbon blacks are available but are still unlikely to be used in elastomer applications due to gaps in the understanding of the effectiveness of carbon blacks when incorporated into elastomer compounds alone or in combination with other carbon blacks, and due to processing challenges, cost, etc. However, these carbon blacks, if used judiciously in elastomer compounds, can improve the performance of elastomer compounds as well as non-functional properties, such as mechanical properties such as tensile strength, elongation at break, modulus, tear strength, break growth, electrical conductivity properties, thermal conductivity properties, color properties, such as L * There is a possibility that the values etc. may change.
[0008] Currently, over 50 grades of hard and soft carbon blacks with a certain range of surface area (iodine adsorption number, nitrogen surface area, etc.), structure (oil absorption number) are commercially available and are used in elastomeric compounds for both tire and non-tire applications. It is known in the art to use these available hard and soft grades of carbon blacks alone or in combination in elastomeric compounds to optimize the general performance properties of the elastomeric compounds covering viscosity, processing, cure, and certain performance characteristics.
[0009] EP0609499A1 or US5430087, a patent entitled Carbon Black Pairs with Different Particle Sizes and Improved Rubber Stocks, discloses the development of improved rubber stocks with unique carbon black systems including unmatched and matched pairs of furnace blacks with fumed silica and silane coupling agents. The carbon black systems include a mixture of large and small particles with high and low structure carbon black pairs. The carbon black systems formulated with polar and non-polar rubbers provide products with a range of desirable properties using only two carbon blacks. Although advanced carbon black compositions including carbon black pairs are claimed and disclosed, fumed silica and silane coupling agents are also part of the claimed carbon black and rubber compound compositions. High surface area carbon blacks (Iodine Adsorption Numbers greater than 160 mg / g) were not selected among the carbon black pairs. The patent also discloses the improvement of color performance (L) of rubber compounds containing the carbon black compositions. * There is no incentive to demonstrate a decline in the value of
[0010] U.S. Patent US6627693B1, entitled "Elastomeric Compositions with Improved Appearance," relates to compositions comprising elastomers and carbon black that may be used to form articles having higher gloss and / or jetness than articles formed using industry standard carbon blacks such as N650. The carbon black has an iodine adsorption value of about 80 to about 400 mg / g, a DBP value of about 50 to about 175 cc / 100 g, a color value of about 100 to about 175% ITRB, a color value of about 80 to about 450 m <2> / g N2SA value and / or about 80 to about 300 m <2> However, in the main claim, each of the values may be characterized by a DBP value of at least about 50 cc / 100 g, a color value of at least about 100% ITRB, and a color value of at least about 80 m, without any upper limit. <2> The advance also described articles made from the compositions, and methods for making the articles. This prior art discloses high surface area (iodine adsorption number 80-400 mg / g) carbon blacks to improve color performance, but the growth of cut resistance decreases with increasing surface area of the carbon black in the rubber compound, and the patent does not disclose or claim carbon black compositions of two or more carbon blacks with varying surface areas.
[0011] European patent EP0866092 entitled "tire with tread of rubber composition containing two different carbon blacks" relates to a tire having a tread made of a rubber composition containing a carbon black reinforcing material as a significant amount of two different carbon blacks and no quantitative amount of silica reinforcing material. This patent disclosed a carbon black composition and a rubber compound based on said carbon black composition. However, the carbon black composition is exclusively a carbon black between hard and soft grades with an iodine adsorption value of up to 130 mg / g, which may or may not contain silica.
[0012] In US Patent US2012 / 0232216A1 entitled "filler blending for rubber formulations corresponding to using a target loading value and target intrinsic properties desired for a rubber formulation," two or more fillers can be combined to create a blend with desired intrinsic properties, i.e., to mimic the desired intrinsic properties of a single filler system. In another exemplary embodiment, by knowing the individual loading amounts of the fillers along with the desired target loading value of the blend and its intrinsic properties, the individual intrinsic properties of at least one unknown filler used to create the blend can be calculated. The unknown filler can then be identified by comparing the calculated intrinsic properties with the intrinsic properties of known fillers. This patent describes a method for producing a blend in which one carbon black is 130m 2 No. 5,393,316 discloses or claims a carbon black composition having a surface area greater than 1 / g.
[0013] From a review of the above prior art, it is apparent that there exists scope and need for the development of carbon black composition grades, including conventional soft and hard grades, having carbon blacks with special features of very high surface area, i.e., very high iodine adsorption number and nitrogen surface area, than conventional hard and soft grades of carbon black, in order to enhance the aesthetics of the article as well as the typical performance behavior of elastomeric compositions comprising said carbon black composition grades having a combination of conventional hard or soft grades of carbon black with such high surface area carbon black. Summary of the Invention [Problem to be solved by the invention]
[0014] It is therefore a primary objective of the present invention to develop a carbon black grade comprising a selective blend of two carbon blacks providing a synergistically improved distribution of aggregate size width ΔD50 and its incorporation into an elastomeric compound of natural rubber, synthetic rubber or a given mixture thereof, providing an elastomeric compound with synergistically improved dispersibility of said carbon blacks.
[0015] Another object of the present invention is to provide a method for producing a iodine adsorption value in the range of about 25 to 160 mg / g, 2 / g~150m 2 A first carbon black having a nitrogen surface area (NSA) in the range of 70 ml / 100 g to 140 ml / 100 g, an oil absorption number (OAN) in the range of 70 ml / 100 g to 140 ml / 100 g, and an iodine adsorption number in the range of 160 mg / g to 300 mg / g, 2 / g~300m 2 and at least one second carbon black, filler 2, having a nitrogen surface area (NSA) in the range of 0.5% to 99.5% by weight, preferably 2.5% to 97.5% by weight, and an oil absorption number (OAN) in the range of 50 ml / 100 g to 120 ml / 100 g, wherein the weight of the second carbon black, filler 2 in the carbon black composition grade varies between 0.5% to 99.5% by weight, preferably 2.5% to 97.5% by weight.
[0016] Another preferred object of the present invention is to provide a method for producing a iodine adsorption value in the range of about 25 to 160 mg / g, 2 / g~150m 2 A first carbon black having a nitrogen surface area (NSA) in the range of 70 ml / 100 g to 140 ml / 100 g, an oil absorption number (OAN) in the range of 70 ml / 100 g to 140 ml / 100 g, and an iodine adsorption number in the range of 160 mg / g to 300 mg / g, 2 / g~300m 2 At least one second carbon black having a nitrogen surface area (NSA) in the range of 50 ml / 100 g to 120 ml / 100 g, and a filler 2, *The objective of the present invention is to provide an elastomeric compound exhibiting a filler value of 0.5% to 99.5% by weight of the carbon black composition grade, and the weight of the second carbon black, filler 2, in the carbon black composition grade varies between 0.5% to 99.5% by weight, preferably between 2.5% to 97.5% by weight of the carbon black composition grade.
[0017] In one aspect of the present invention, the iodine adsorption value is in the range of about 25 to 160 mg / g, and the iodine adsorption value is in the range of about 20 to 160 mg / g. 2 / g~150m 2 A first carbon black having a nitrogen surface area (NSA) in the range of 70 ml / 100 g to 140 ml / 100 g, an oil absorption number (OAN) in the range of 70 ml / 100 g to 140 ml / 100 g, and an iodine adsorption number in the range of 160 mg / g to 300 mg / g, 2 / g~300m 2 and at least one second carbon black, filler 2, having a nitrogen surface area (NSA) in the range of 0.5 wt.% to 99.5 wt.% of the carbon black composition grade, preferably between 2.5 wt.% to 97.5 wt.%. The elastomeric compound comprising at least one second carbon black, filler 2, having a nitrogen surface area (NSA) in the range of 0.5 wt.% to 99.5 wt.% of the carbon black composition grade, exhibits improved tear strength, and the weight of the second carbon black, filler 2, in the carbon black composition grade varies between 0.5 wt.% to 99.5 wt.%, preferably between 2.5 wt.% to 97.5 wt.%.
[0018] In another aspect of the present invention, the iodine adsorption value is within the range of about 25 to 160 mg / g, and the iodine adsorption value is within the range of about 20 to 160 mg / g. 2 / g~150m 2 A first carbon black having a nitrogen surface area (NSA) in the range of 70 ml / 100 g to 140 ml / 100 g, an oil absorption number (OAN) in the range of 70 ml / 100 g to 140 ml / 100 g, and an iodine adsorption number in the range of 160 mg / g to 300 mg / g, 2 / g~300m 2The elastomeric compound comprising at least one second carbon black, filler 2, having a nitrogen surface area (NSA) in the range of 0.5 wt.% to 99.5 wt.% of the carbon black composition grade, and an oil absorption number (OAN) in the range of 50 ml / 100 g to 120 ml / 100 g, exhibits improved shear growth, and the weight of the second carbon black, filler 2, in the carbon black composition grade varies between 0.5 wt.% to 99.5 wt.%, preferably between 2.5 wt.% to 97.5 wt.% of the carbon black composition grade.
[0019] Another object of the present invention is to provide a method for producing a iodine adsorption value in the range of about 25 to 160 mg / g, 2 / g~150m 2 A first carbon black having a nitrogen surface area (NSA) in the range of 70 ml / 100 g to 140 ml / 100 g, an oil absorption number (OAN) in the range of 70 ml / 100 g to 140 ml / 100 g, and an iodine adsorption number in the range of 160 mg / g to 300 mg / g, 2 / g~300m 2 and at least one second carbon black having a nitrogen surface area (NSA) in the range of 0.5% to 99.5% by weight, preferably 2.5% to 97.5% by weight of the carbon black composition grade.
[0020] Another object of the present invention is to provide a method for producing a iodine adsorption value in the range of about 25 to 160 mg / g, 2 / g~150m 2 A first carbon black having a nitrogen surface area (NSA) in the range of 70 ml / 100 g to 140 ml / 100 g, an oil absorption number (OAN) in the range of 70 ml / 100 g to 140 ml / 100 g, and an iodine adsorption number in the range of 160 mg / g to 300 mg / g, 2 / g~300m 2and at least one second carbon black having a nitrogen surface area (NSA) in the range of 0.5% to 99.5% by weight, preferably 2.5% to 97.5% by weight of the carbon black composition grade. [Means for solving the problem]
[0021] In a basic embodiment, the present invention provides a carbon black composition comprising a high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m / g, an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, and processability for making elastomeric compounds, the carbon black composition comprises a synergistic combination of high surface area carbon blacks comprising (a) a first carbon black having an iodine adsorption number in the range of 30.5-146.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5-139.9 m / g, and an oil absorption number (OAN) in the range of 73-121.4 ml / 100 g, and (b) a second carbon black having an iodine adsorption number in the range of 162.0-292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0-294.0 m / g, and an oil absorption number (OAN) in the range of 50-120 ml / 100 g, the high surface area carbon blacks in the carbon black composition selectively varying between 0.5% and 50% by weight; the carbon black composition provides a synergistically improved breadth ΔD50 of aggregate size distribution of the carbon black composition for each of the first carbon black and the high surface area carbon black; the value of the synergistically improved width ΔD50 of the aggregate size distribution of the carbon black composition is improved when the second carbon black in the carbon black composition varies between 0.5 wt.% and 50 wt.%; The carbon black composition incorporating the high surface area carbon black provides a carbon black composition having desirable processability and dispersibility in an elastomeric compound in the range of 87.71 to 99.87%, and improved mechanical properties including, selectively, tear strength, elongation at break, or tensile strength of the elastomeric compound.
[0022] Another embodiment of the present invention relates to a carbon black composition having a synergistically enhanced width of the aggregate size distribution, ΔD50, expressed as full width at half maximum, in the range of 50 nm to 160 nm, and wherein the ratio of the mass weighted average aggregate size, Dw, and the number weighted average aggregate size, DN, of said carbon black composition is in the range of 1.4 to 4.02.
[0023] Another embodiment of the present invention relates to a carbon black composition, wherein the magnitude of the spread of the curve of the distribution, defined by the ratio of the width to the mode of the distribution, ΔD50 / DMode, is in the range of 0.63 to 0.9.
[0024] Yet another embodiment of the present invention relates to a carbon black composition, wherein depending on the selective combination of the first carbon black and the second carbon black, the aggregate size distribution of the carbon black composition is a unimodal aggregate size distribution or a bimodal aggregate size distribution.
[0025] In a further embodiment of the present invention, the carbon black composition comprises, in weight % combinations, of any of N339, N134, N660, N774, and N550 as the first carbon black and any of EXP1, EXP2, and EXP3 as the second carbon black: N339:EXP1=95% by weight:05% by weight, N339:EXP1=90% by weight:10% by weight, N339:EXP1=85% by weight:15% by weight, N339:EXP1=80% by weight:20% by weight, N339:EXP1=75% by weight:25% by weight, N339:EXP1=70% by weight:30% by weight, N339:EXP1=60% by weight:40% by weight, N339:EXP1=50% by weight:50% by weight, N134:EXP1=50% by weight:50% by weight, N134:EXP1=80% by weight:20% by weight, N134:EXP1=70% by weight:30% by weight, N660:EXP1=50% by weight:50% by weight, N660:EXP1=80% by weight:20% by weight, N660:EXP1=70% by weight:30% by weight, N774:EXP1=80% by weight:20% by weight, N774:EXP1=70% by weight:30% by weight, N774:EXP1=50% by weight:50% by weight, N774:EXP3=50% by weight:50% by weight, N550:EXP1=80% by weight:20% by weight, N550:EXP1=70% by weight:30% by weight, N550:EXP1=50% by weight:50% by weight, N550:EXP2=50% by weight:50% by weight, Including, EXP1 is B219 having an iodine adsorption number of 256.75 mg / g, a nitrogen surface area of 262.98 m2 / g, and an oil absorption number of 94.8 ml / 100 g; EXP3 is B361 having an iodine adsorption number of 292.0 mg / g, a nitrogen surface area of 294.0 m2 / g, and an oil absorption number of 70.0 ml / 100 g; The EXP2 is N115 having an iodine adsorption number of 162 mg / g, a nitrogen surface area of 156 m / g, and an oil absorption number of 115 ml / 100 g.
[0026] A further embodiment of the present invention relates to a carbon black composition comprising: P23 having 95% by weight of N339 and 0.5% by weight of B219; P24 having 90% by weight of N339 and 10% by weight of B219; P25 having 85% by weight of N339 and 15% by weight of B219; P26 having 80% by weight of N339 and 20% by weight of B219; P29 having 70% by weight of N339 and 30% by weight of B219; P30 having 60% by weight of N339 and 40% by weight of B219; P31 having 50% by weight of N339 and 50% by weight of B219; Either The N339 has an iodine adsorption number of 89.0 mg / g, a nitrogen surface area of 86.2 m2 / g, and an oil absorption number of 119.8 ml / 100 g; The carbon black composition comprises a carbon black composition having a width and a spread of 0.625 to 0.93, the width and spread increasing with increasing weight percent of B219 as the second carbon black relative to N339 as the first carbon black in the carbon black composition.
[0027] Another embodiment of the present invention relates to a carbon black composition comprising: P37 having 80% by weight of N134 and 20% by weight of B219; P36 having 50% by weight of N339 and 50% by weight of B219; Either The N134 has an iodine adsorption number in the range of 146.75.0 mg / g, a nitrogen surface area of 139.9 m2 / g, and an oil absorption number of 121.4 ml / 100 g; wherein the width value and the magnitude of the spread increase from 55 nm and 0.695 to 58 nm and 0.88 with increasing weight percent of the B219 as the second carbon black relative to the N134 as the first carbon black in the carbon black composition.
[0028] Yet another embodiment of the present invention is a carbon black composition comprising: P40 having 80% by weight of said N660 and 20% by weight of said B219; P39 having 50% by weight of said N660 and 50% by weight of said B219; Either The N660 has an iodine adsorption number of 37.5 mg / g, a nitrogen surface area of 35.1 m2 / g, and an oil absorption number of 91.2 ml / 100 g; the width value and the magnitude of the spread do not change with increasing weight percent of B219 as the second carbon black relative to N660 as the first carbon black in the carbon black composition; Or, The carbon black composition comprises: P42 having 80% by weight of N774 and 20% by weight of B219; P43 having 70% by weight of N774 and 30% by weight of B219; P44 having 50% by weight N774 and 50% by weight B219; Either The N774 has an iodine adsorption value of 30.5 mg / g, a nitrogen surface area of 31.5 m2 / g, and an oil absorption value of 73.0 ml / 100 g; the width value and the magnitude of the spread increase from 186 nm and 1.038 to 192 nm and 1.162 with an increase in the weight percent of the B219 as the second carbon black relative to the N774 as the first carbon black in the carbon black composition; Or, The carbon black composition comprises: P52 having 80% by weight of N550 and 20% by weight of B219; P53 with 70% by weight N550 and 30% by weight B219; P54 having 50% by weight of N550 and 50% by weight of B219; P61 having 50% by weight of N550 and 50% by weight of N115; Either The N550 has an iodine adsorption value of 43.2 mg / g and a nitrogen surface area of 36.09 m2 / g. , and has an oil absorption value of 119.6 ml / 100 g; wherein the width value and the magnitude of the spread change from 161 nm and 0.865 to 155 nm and 1.122 with increasing weight percent of the B219 as the second carbon black relative to the N550 as the first carbon black in the carbon black composition.
[0029] According to a preferred embodiment of the present invention, there is provided an elastomer compound incorporating a carbon black composition, said elastomer compound comprising: (I) A carbon black composition comprising a high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, (a) at least one first carbon black having an iodine adsorption number in the range of 30.5 to 146.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m2 / g, and an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g; and (b) at least a second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, a carbon black composition, wherein the high surface area carbon black in the carbon black composition is selectively varied between 0.5% and 50% by weight, the carbon black composition providing a synergistically enhanced width ΔD50 of aggregate size distribution of the carbon black composition for each of the first carbon black and the high surface area carbon black, the value of the synergistically enhanced width ΔD50 of aggregate size distribution of the carbon black composition being improved when the second carbon black in the carbon black composition is varied between 0.5% and 50% by weight; (II) elastomeric rubber compounds, including NR / BR, SBR / BR, NBR, EPDM, and IIR, The carbon black composition contains high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, and has desirable processability and dispersibility in an elastomeric compound in the range of 87.71 to 99.87%, and improved mechanical properties, selectively including tear strength, elongation at break, or tensile strength, of the elastomeric compound. The present invention relates to providing an elastomeric compound.
[0030] In another embodiment of the present invention, the ratio of the carbon black composition to the rubber compound is in the range of 0.5 phr to 150 phr, Improved aesthetic and color properties, including L* values in the range of 15.38 to 5.05; The tear strength is within the range of 33N / mm to 198N / mm. The present invention relates to providing the elastomer compound having an elongation at break of 240% to 750%.
[0031] In another embodiment of the present invention, the carbon black composition comprises N339 as the first carbon black and B219 as the second carbon black; the B219 is 50 wt.% of the carbon black composition, which is 45 phr total; The elastomer compound is directed to providing an elastomer compound that achieves a tear strength in the range of 145 N / mm to 155 N / mm.
[0032] In yet another embodiment of the present invention, the carbon black composition comprises N660 as the first carbon black and B219 as the second carbon black; the B219 is 50 wt.% of the carbon black composition, which is 45 phr total; The elastomer compound is directed to providing an elastomer compound that achieves a tear strength in the range of 95 N / mm to 110 N / mm.
[0033] In another embodiment of the present invention, the carbon black composition comprises N134 as the first carbon black and B219 as the second carbon black; the B219 is 50 wt.% of the carbon black composition, which is 45 phr total; The elastomer compound is directed to providing an elastomer compound that achieves a tear strength in the range of 195 N / mm to 210 N / mm.
[0034] A further embodiment of the present invention is a carbon black composition comprising N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the carbon black composition; Or, the carbon black composition comprising N774 as the first carbon black and B361 as the second carbon black; the B361 is 50% by weight of the carbon black composition; The elastomer compound exhibits a tear strength of 45 N / mm to 55 N / mm. The present invention relates to providing said elastomer compound.
[0035] A further embodiment of the present invention is a carbon black composition comprising N134 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a tear strength of 100 N / mm to 115 N / mm.
[0036] A further embodiment of the present invention is a carbon black composition comprising N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a tear strength of 70 N / mm to 85 N / mm. The present invention relates to providing said elastomer compound.
[0037] A further embodiment of the present invention is a carbon black composition comprising N550 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; Or, the carbon black composition comprising N550 as the first carbon black and N115 as the second carbon black; the N115 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a tear strength of 40 N / mm to 55 N / mm. The present invention relates to providing said elastomer compound.
[0038] Another embodiment of the present invention is a carbon black composition comprising N339 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 5.5 to 3.5. The present invention relates to providing said elastomer compound.
[0039] Another embodiment of the present invention is a carbon black composition comprising N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 10.5 to 9.5. The present invention relates to providing said elastomer compound.
[0040] Yet another embodiment of the present invention is a carbon black composition comprising N134 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 10.5 to 9.5. The present invention relates to providing said elastomer compound.
[0041] A further embodiment of the present invention is a carbon black composition comprising N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 7.8 to 6.8. The present invention relates to providing said elastomer compound.
[0042] A further embodiment of the present invention is a carbon black composition comprising N660 as the first carbon black and B361 as the second carbon black; the B361 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 7.5 to 6.5. The present invention relates to providing said elastomer compound.
[0043] A further embodiment of the present invention is a carbon black composition comprising N550 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 6.5 to 5.5. The present invention relates to providing said elastomer compound.
[0044] Another embodiment of the present invention is a carbon black composition comprising N550 as the first carbon black and N115 as the second carbon black; the N115 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 8.5 to 7.5. The present invention relates to providing said elastomer compound.
[0045] Another embodiment of the present invention is a carbon black composition comprising N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a break growth of 10.0 mm to 9.0 mm at 10KC and 15.0 mm to 14.0 mm at 20KC when loaded with 45 phr of total carbon black. The present invention relates to providing said elastomer compound.
[0046] Yet another embodiment of the present invention is a carbon black composition comprising N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a break growth of 13.0 mm to 12.0 mm at 10 KC when loaded with 70 phr of total carbon black. The present invention relates to providing said elastomer compound.
[0047] A further embodiment of the present invention is a carbon black composition comprising N134 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a break growth of 9.0 mm to 8.0 mm for 10KC and 13.0 mm to 12.0 mm for 20KC when loaded with 60 phr of total carbon black. The present invention relates to providing said elastomer compound.
[0048] A further embodiment of the present invention is a carbon black composition comprising N339 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprises N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprising N550 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprising N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an elongation at break of 240% to 750%. The present invention relates to providing said elastomer compound.
[0049] A further embodiment of the present invention is a carbon black composition comprising N339 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprises N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprising N550 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprising N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer blend exhibits a tensile strength of 6.0 MPa to 28.0 MPa. The present invention relates to providing said elastomer compound.
[0050] According to a preferred embodiment of the present invention, there is provided a process for producing a carbon black composition, comprising the steps of: The carbon black has an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, and is processable to prepare an elastomeric compound; providing a synergistic combination of the high surface area carbon blacks, the high surface area carbon blacks including: (a) a first carbon black having an iodine adsorption number in the range of 30.5 to 146.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m / g, and an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g; and (b) a second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g; the high surface area carbon black in the carbon black composition selectively varies between 0.5% and 50% by weight; the carbon black composition provides a synergistically improved breadth ΔD50 of aggregate size distribution of the carbon black composition for each of the first carbon black and the high surface area carbon black; the value of the synergistically improved width ΔD50 of the aggregate size distribution of the carbon black composition is improved when the second carbon black in the carbon black composition varies between 0.5 wt.% and 50 wt.%; The carbon black composition incorporating the high surface area carbon black has desirable processability and dispersibility in an elastomeric compound in the range of 87.71 to 99.87%, and improved mechanical properties including, selectively, tear strength, elongation at break, or tensile strength of the elastomeric compound.
[0051] Another aspect of the present invention is a process for producing an elastomeric compound incorporating a carbon black composition, comprising the steps of: comprising a high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, and processability for preparing an elastomeric compound; I) providing a carbon black composition comprising: (a) at least one first carbon black having an iodine adsorption number in the range of 30.5 to 146.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m2 / g, and an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g; and (b) at least a second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g; the high surface area carbon black in the carbon black composition selectively varies between 0.5% and 50% by weight; the carbon black composition provides a synergistically enhanced width ΔD50 of aggregate size distribution of the carbon black composition for each of the first carbon black and the high surface area carbon black, the value of the synergistically enhanced width ΔD50 of aggregate size distribution of the carbon black composition being improved when the amount of the second carbon black in the carbon black composition varies between 0.5% and 50% by weight; II) incorporating said carbon black composition into an elastomeric rubber according to a conventional process for the manufacture of elastomeric compounds; The present invention relates to a method for producing an elastomeric polyimide having desirable processability and dispersibility in the range of 87.71 to 99.87% in an elastomeric compound, and improved mechanical properties, optionally including tear strength, elongation at break, or tensile strength of the elastomeric compound.
[0052] Another aspect of the present invention is a carbon black composition comprising: (a) at least one first carbon black having an iodine adsorption number in the range of 30.5 to 146.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m / g, and an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g; and (b) at least one second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160 to 294.0 m / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g; and a rubber compound; the second carbon black in the carbon black composition varies in the range of 0% by weight to 50% by weight; the carbon black composition has a width of aggregate size distribution, expressed as a full width at half maximum, said width increasing with increasing weight percentage of the second carbon black in the carbon black composition within said range; The width is within a range of 63 nm to 88 nm when the first carbon black is N339, within a range of 55 nm to 58 nm when the first carbon black is N134, and within a range of 153 nm to 157 nm when the first carbon black is N660; the ratio of the mass weighted average aggregate size DW to the number weighted average aggregate size DN of the carbon black composition is in the range of 1.4 to 2 when the first carbon black is N339, in the range of 1.4 to 1.52 when the first carbon black is N134, and in the range of 1.57 to 4.02 when the first carbon black is N660; the magnitude of the spread of the curve of the distribution, defined by the ratio of the width to the mode of the distribution, is in the range of 0.63 to 0.9 when the first carbon black is N339, in the range of 0.77 to 0.88 when the first carbon black is N134, and in the range of 0.83 to 0.88 when the first carbon black is N660; The present invention relates to providing an elastomeric compound.
[0053] Yet another aspect of the present invention is a rubber composition comprising at least one of NR / BR, SBR / BR, NBR, EPDM and IIR; The elastomer compound has an improved dispersion of carbon black in the elastomer compound within the range of 87.71 to 99.87%. The present invention relates to providing an elastomeric compound.
[0054] A further aspect of the invention is a composition having an L* value in the range of 15.38 to 5.05; Tear strength within the range of 33N / mm~198N / mm, Cutting growth in the range of 26.38mm~8.78mm, Tensile strength in the range of 5.57MPa~25.06MPa; Elongation at break in the range of 208% to 732% Selectively having aesthetic, color and mechanical properties including The present invention relates to providing an elastomeric compound. [Brief description of the drawings]
[0055] [Figure 1]Carbon black composition, P22 (N339:EXP1-100:00), P23 (N339:EXP1-95:05), P24 (N339:EXP1-90:10), P25 (N339:EXP1-85:15), P26 (N339:EXP1-80:20), P27 (N339:EXP1-75:25), P29 (N339:EXP1-70:30), P30 (N339:EXP1-60: 40), P31(N339:EXP1-50:50), P28(N339:EXP1-00:100);P32(N234:EXP1-100:00), P33(N234:EXP1-75:25) ;P35(N134:EXP1-100:00), P37(N134:EXP1-80:20), P58(N134:EXP1-70:30), P36(N134:EXP1-50:50);P38 (N660:EXP1-100:00), P40(N660:EXP1-80:20), P48(N660:EXP1-70:30), P39(N660:EXP1-50:50), P51(N55 0:EXP1-100:00), P52(N550:EXP1-80:20), P53(N550:EXP1-70:30), P54m(N550:EXP1-50:50);P61(N550:E Figure 1 shows tinting strength units including: P62(N550:EXP2-00:100); P41(N774:EXP1-100:00), P42(N774:EXP1-80:20), P43(N774:EXP1-70:30), P44C(N774:EXP1-50:50), P63(N774:EXP3-50:50), P64C(N774:EXP3-00:100). [Diagram 2] FIG. 1 shows differential volume distribution of aggregate size for (1) P22 (N339:EXP1=100:0.0), (2) P28 (EXP1 100), (3) P26 (N339:EXP1=80:20), (4) P29 (N339:EXP1=70:30), (5) P30 (N339:EXP1=60:40), and (6) P31 (N339:EXP1=50:50). [Diagram 3]FIG. 1 shows differential volume distribution of aggregate sizes for (1) P35 (N134:EXP1=100:00), (2) P28 (EXP1 100), (3) P37 (N134:EXP1=80:20) and (4) P36 (N134:EXP1=50:50). [Figure 4] FIG. 1 shows differential volume distribution of aggregate sizes for (1) P38 (N660:EXP1=100:00), (2) P28 (EXP1=100), (3) P40 (N660:EXP1=80:20) and (4) P39 (N660:EXP1=50:50). [Diagram 5] FIG. 1 shows ΔD50 for carbon black compositions P22 (N339:B219=100:00), P24 (N339:B219=90:10), P25 (N339:B219=85:15), P26 (N339:B219=80:20), P29 (N339:B219-70:30), P30 (N339:B219=60:40), P31 (N339:B219=50:50) and P28 (B219 100). [Figure 6] FIG. 13 shows ΔD50 / mode for carbon black compositions P22 (N339:B219=100:00), P24 (N339:B219=90:10), P25 (N339:B219=85:15), P26 (N339:B219=80:20), P29 (N339:B219-70:30), P30 (N339:B219=60:40), P31 (N339:B219=50:50) and P28 (B219 100). [Figure 7] FIG. 1 shows ΔD50 for carbon black compositions P35 (N134:B219=100:00), P37 (N134:B219=80:20), P36 (N134:B219=50:50), and P28 (B219 100). [Figure 8] FIG. 1 shows ΔD50 / mode for carbon black compositions P35 (N134:B219=100:00), P37 (N134:B219=80:20), P36 (N134:B219=50:50), and P28 (B219 100). [Figure 9]FIG. 1 shows the ΔD50 of carbon black compositions P38 (N660:B219=100:00), P28 (B219 100), P40 (N660:B219=80:20) and P39 (N660:B219=50:50). [Figure 10] FIG. 1 shows ΔD50 / mode for carbon black compositions P38 (N660:B219=100:00), P28 (B219 100), P40 (N660:B219=80:20) and P39 (N660:B219=50:50). [Figure 11] Different carbon black compositions, P23C (N339:EXP1-95:05), P24C (N339:EXP1-90:10), P25C (N339:EXP1-85:15), P26C (N339:EXP1-80:20), P27C (N339:EXP1-75:25), P29C (N339:EXP1-70:30), P30C (N339:EXP1-85:15), P26C (N339:EXP1-80:20), P27C (N339:EXP1-75:25), P29C (N339:EXP1-70:30), P30C (N339:EXP1-85:15), P26C (N339:EXP1-80:20), P30C (N339:EXP1-85:15), P27C (N339:EXP1-85:25), P29C (N339:EXP1-80:30), P30C (N339:EXP1-85:15 ... P1-60:40, P31C(N339:EXP1-50:50);P37C(N134:EXP1-80:20),P36C(N134:EXP1-50:50);P40C( N660:EXP1-80:20), P39C(N660:EXP1-50:50); P57C(N134:EXP1-80:20), P58C(N134:EXP1-70:3 0), P59C(N134:EXP1-50:50); P47C(N660:EXP1-80:20), P48C(N660:EXP1-70:30), P49C(N660: EXP1-50:50), P50C(N660:EXP1-00:100);P52C(N550:EXP1-80:20),P53C(N550:EXP1-70:30),P FIG. 1 shows the tear strength of elastomeric compounds including P54C (N550:EXP1-50:50), P61C (N550:EXP2-50:50), P62C (N774:EXP1-80:20), P43C (N774:EXP1-70:30), P44C (N774:EXP1-50:50), and P63C (N774:EXP3-50:50). [Figure 12]FIG. 1 shows the change in severance growth for various elastomeric compounds with different carbon black compositions, P29C (N339:EXP1-70:30), P31C (N339:EXP1-50:50); P40C (N339:EXP1-80:20), P39C (N660:EXP1-50:50); P59C (N134:EXP1-50:50); P49C (N660:EXP1-50:50); P44C (N774:EXP1-50:50), P63C (N774:EXP3-50:50). [Figure 13] Different carbon black compositions, P23C (N339:EXP1-95:05), P24C (N339:EXP1-90:10), P25C (N339:EXP1-85:15), P26C (N339:EXP1-80:20), P27C (N339:EXP1-75:25), P29C (N339:EXP1-70:30), P30C (N339:EXP1-60:40), P31C ( FIG. 1 shows the change in L* value of elastomer compounds including N339:EXP1-50:50; P39C (N660:EXP1-50:50); P59C (N134:EXP1-50:50); P54C (N550:EXP1-50:50), P61C (N550:EXP2-50:50); P44C (N774:EXP1-50:50), P63C (N774:EXP3-50:50). [Figure 14] FIG. 1 shows tested and calculated L* values of elastomeric compounds including different carbon black compositions, P23C (N339:EXP1-95:05), P24C (N339:EXP1-90:10), P25C (N339:EXP1-85:15), P26C (N339:EXP1-80:20), P27C (N339:EXP1-75:25) P29C (N339:EXP1-70:30), P30C (N339:EXP1-60:40), and P31C (N339:EXP1-50:50). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0056] Materials used Rubber 1. Natural Rubber (NR)- Commercially available Ribbed Smoked Sheet (RSS) of 50+-5 ML (1+4) 100°C from Indian Rubber Board, Kottayam. 2. Polybutadiene (BR)- Commercially available Reflex 1220 with 96% cis content from Reliance Industries Ltd. India. 3. Styrene Butadiene Rubber (SBR)- Commercially available oil extended (37.5 wt%) SBR containing 23.5 parts styrene from Reliance Industries Ltd., India. 4. Ethylene Propylene Diene Monomer (EPDM) based rubber- commercially available from Rajshila Synthetics Pvt. Ltd., India (ENB-5.7%, ethylene 65% and propylene 35%). 5. Nitrile Butadiene Rubber (NBR)- Commercially available NBR from Anant Poly Rubb Pvt. Ltd., India (Acrylonitrile content- 35%). 6. Butyl Rubber (IIR) – commercially available supplied by Flexils Pvt. Ltd, India
[0057] Filler 7. Semi-reinforced carbon black - The carbon black used in the present invention is as follows. i) Hard carbon black - N339, iodine adsorption number, 89.00 mg / g; nitrogen surface area (NSA), 86.2 m2 / g; oil absorption number (OAN), 119.8 ml / 100 g; Phillips Carbon Black Limited (PCBL). ii) Hard Carbon Black-N134, Iodine Adsorption Number, 146.75mg / g; NSA, 139.90m2 / g; Oil Absorption Number (OAN), 121.4ml / 100g; PCBL. iii) Hard carbon black-N234, Iodine adsorption number, 121.5mg / g; NSA, 115.8m2 / g; Oil absorption number (OAN), 121.9ml / 100g; PCBL. iv) Soft carbon black-N550, iodine adsorption number, 43.20 mg / g; NSA, 36.09 m2 / g; oil absorption number (OAN), 119.6 ml / 100 g; PCBL. v) Soft carbon black-N774, iodine adsorption number, 30.50 mg / g; NSA, 31.5 m2 / g; oil absorption number (OAN), 73.0 ml / 100 g; PCBL. vi) Soft Carbon Black-N660, Iodine Adsorption Number, 37.50mg / g; NSA, 35.10m2 / g; Oil Absorption Number (OAN), 91.2ml / 100g; PCBL.
[0058] The specific carbon blacks that may be used in this invention are as follows: vii) EXP1 B219, Iodine adsorption number, 256.75mg / g; NSA 262.98m2 / g; Oil absorption number (OAN), 94.8ml / 100g; PCBL. viii) EXP2(N115)-Iodine adsorption number 162.00mg / g; NSA 156.00m2 / g; Oil absorption number 115.0ml / 100g; PCBL. ix) EXP3 (B361) - Iodine adsorption number 292.00 mg / g; NSA 294.00 m2 / g; Oil absorption number 70.0 ml / 100 g; PCBL.
[0059] Rubber curing system 8. Hardener- Sulphur Powder (99.5% purity) from Loba Chemie Pvt.Ltd. 9. Accelerators- N-Cyclohexyl-2-benzothiazole sulfenamide (CBS) from NOCIL Ltd., India. 2-Mercaptobenzothiazole (MBT), Tetramethylthiuram disulfide (TMTD), (2,2'Dibenzothiazyl disulfide or 2,2'-Dithiobisbenzothiazole (MBTS), and Zinc dibutyl dithiocarbonate (ZDBC), all from Advance Chemical Pvt. Ltd., India. 10. Inhibitors- N-(Cyclohexylthio)phthalimide (CTP, PVI)- A non-staining and non-discoloring vulcanization inhibitor, NOCIL Ltd., India. 11. Activators – Zinc Oxide (ZnO) for rubber vulcanization from Avantor Performance Materials India Ltd., India, and Stearic Acid from Loba Chemie Pvt. Ltd., India.
[0060] Stabilizer 12. Heat stabilizer- 2,2,4-Trimethyl-1,2-dihydroquinoline (TMQ) from NOCIL Ltd., India. 13. Weathering stabilizer - N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) containing 27.5 parts of highly aromatic oil. 14. Microcrystalline wax - protection against ozone attack.
[0061] Processing Aids 15. Oils- Aromatic oil from Viswaat Chemicals Ltd., India; Paraffinic oil supplied by Advance Chemical Pvt.Ltd., India DOP oil supplied by Vraj Chem Pvt Ltd., India. 16. Peptizer- For viscosity control from NOCIL Ltd., India.
[0062] Equipment used: 1.Banbury Mixer-Kobelco, Japan. 2.Two Roll Mill-Santosh Engineering Pvt.Ltd., India. 3. Forming Press-Santosh Engineering Pvt.Ltd., India. 4. Oscillating Disc Rheometer (ODR)-ODR2000, Alfa Technology, USA. 5. Universal Testing Machine (UTM) - Instron 3366, Instron, UK. 6. Rubber Process Analyzer (RPA)-RPA93001, Alfa Technology, USA. 7.Demattia Flexure Testing Machine-Serial No. 6501.1.1, Prolific engineers, India. 8. Aggregate Size Analyzer-BI-DCP, Brookhaven Instrument Corporation, USA. 9.Spectrophotometer-AGERA Spectrophotometer, Hunter lab, USA. 10. Tint Tester-Tint Tester 527, Erichsen, USA. 11. Spectrophotometer-HITECH, DABS, Luxemdourg, Germany. 12. Dispersion Evaluator-91001SR, Alfa technology, USA.
[0063] Preparation of Carbon Black Composition Grades The carbon black composition grade of a given composition may comprise a first carbon black having an iodine adsorption number in the range of about 25-160 mg / g, preferably in the range of about 40-150 mg / g; a nitrogen surface area (NSA) in the range of 20-150 m2 / g, preferably in the range of 35-140 m2 / g; an oil absorption number (OAN) in the range of 70-140 ml / 100 g, more preferably in the range of 80-125 ml / 100 g; and a second ...160-300 mg / g; 2 and at least one second carbon black, Filler 2, having a nitrogen surface area in the range of 100 / g and an oil absorption number (OAN) in the range of 50-120 ml / 100 g, the weight of the second carbon black, Filler 2, in the carbon black composition grade varies between 0.5% by weight and 99.5% by weight. Filler 1 and Filler 2 can be selected in the form of pellets or powder. Selected predetermined compositions of "Filler 1" and "Filler 2" are shown in Table 1. In this patent application, the terms carbon black composition and carbon black composition grade are used interchangeably.
[0064] Table 1 Carbon black composition grades TIFF2025024063000002.tif193170 TIFF2025024063000003.tif109170 Filler 1 - N339, N660, N134, N234, N550, N774; Filler 2 - EXP1, EXP2, EXP3; Feed time 30min.
[0065] In the present invention, the first carbon black, "Filler 1", is selected from conventional hard and soft grade carbon blacks of the N100, N200, N300, N500, N600, N700 series, or chemically treated, preferably coupling agent treated, organic group-containing or sulfur-containing compound treated carbon blacks of the N100, N200, N300, N500, N600 and N700 series.
[0066] The “Filler 1” and “Filler 2” carbon black composition grades can also be made using any other conventional filler mixing technique followed by granulation, including a granulator using an appropriate amount of water, molasses, or sugar solution as a binder.
[0067] The carbon black composition grades containing "filler 1" and "filler 2" are preferably prepared in a drum-shaped blender of maximum volume capacity of 10 liters, with the option of two inlet positions for the carbon black used to prepare the carbon black composition grades, and one discharge position at the bottom of the blender, followed by granulation. There is an option for mounting an agitator, such as a paddle or ribbon, inside the blender. However, to avoid breakage of the carbon black pellets due to strong shear forces caused by the agitator, the carbon black composition containing "filler 1" and "filler 2" is preferably prepared under convection forces by 360° rotation with continuous clockwise and counterclockwise motions. Other blenders such as "V" blenders, double cone blenders, granulators and grinding processes can also be used to prepare the present carbon black composition grades.
[0068] If the carbon black composition is prepared from carbon black powder, a ribbon blender, paddle blender, granulator, or plow shear mixer of any capacity can also be used to prepare the present carbon black composition grades.
[0069] The drum blender can be manually filled with a predetermined weight of carbon black through two inlet locations present at the top of the blender, and ultimately the carbon black can be mixed by a 360° rotational motion of the blender with continuous clockwise and counterclockwise rotation at about 100 to about 200, about 10 to 100 rpm for up to 12 hours, up to 6 hours, about 5 minutes to about 6 hours, or any other predetermined time in between.
[0070] The blender can also be filled with a predetermined weight of carbon black through two loss-in-weight feeders located above the two inlet locations of the blender under vibration mode, one feeder feeding one first carbon black, "filler 1" and the other feeder feeding one second carbon black, "filler 2". Once a total of 5 kg of one first carbon black, "filler 1", and one second carbon black, "filler 2" are incorporated into the blender, the feeders stop feeding fillers in the blender, the openings of the inlet locations are closed, and "filler 1" and "filler 2" are mixed by 360° tumbling of the blender with continuous clockwise and counterclockwise rotation at about 100 to about 200, or about 10 to 100 rpm for 12 hours or less, for 6 hours or less, for about 5 minutes to about 6 hours, or any other predetermined time in between.
[0071] Carbon black composition grades and granules can be made in a granulator equipped with a main rotor and chopper that can rotate at different rotational speeds. A given carbon black composition (Table 1) is introduced into the granulator along with the required amount of water, molasses or sugar solution and granulated for at least 15 minutes to make the granules.
[0072] Carbon black composition grades and granules can be further produced in-process during carbon black manufacturing by incorporating Filler 1 and Filler 2 in the presence of water and a binder solution such as molasses, sugar, lignosulfonate, etc., into a pelletizer, followed by a drying process.
[0073] Example 1 Preparation of P23: Make a 5 kg batch of sample P23 by feeding one first carbon black from feeder 1, "filler 1", carbon black pellets of N339, and one second carbon black from feeder 2, "filler 2", carbon black pellets of EXP1, through the two inlet positions of the blender for 30 minutes at feeding rates of 9.5 kg / h and 0.5 kg / h, respectively. After 30 minutes, switch off the feeder and close the two inlet positions of the blender with lids. Mix the added carbon black in the blender by sequentially rotating the blender chamber 360° in a clockwise direction and then in a counterclockwise direction for 5 minutes at about 25 rpm to about 50 rpm. After 5 minutes, store the carbon black composition in a sealed aluminum container for further use in the development of elastomeric compounds.
[0074] Examples 2 to 10 Preparation of P24-P33: Employ the same process as described in Example 1 above to make samples P24-P33 of 5 kg batches each according to the carbon black composition, amount of carbon black (kg) and feeding rate (kg / h) disclosed in Table 1. Store the carbon black composition in a sealed aluminum container for further use in the development of elastomeric compounds.
[0075] Example 11, Example 13 and Example 14 Preparation of P36, P37 and P58: Employing the same process as described in Example 1 above, prepare samples P36, P37 and P58 of 5 kg each batch according to the carbon black composition, amount of carbon black (kg) and feeding rate (kg / h) disclosed in Table 1. Store the carbon black composition in a sealed aluminum container for further use in the development of elastomeric compounds.
[0076] Examples 15 to 17 Preparation of P39, P40 and P48: Employing the same process described in Example 1 above, prepare samples P39, P40 and P48 of 5 kg each batch according to the carbon black composition, amount of carbon black (kg) and feeding rate (kg / h) disclosed in Table 1. Store the carbon black composition in a sealed aluminum container for further use in the development of elastomeric compounds.
[0077] Examples 18 to 21 Preparation of P42-P44 and P63: Employ the same process as described in Example 1 above to make samples P42-P44 and P63 of 5 kg each batch according to the carbon black composition, amount of carbon black (kg) and feeding rate (kg / h) disclosed in Table 1. Store the carbon black compositions in sealed aluminum containers for further use in the development of elastomeric compounds.
[0078] Example 22 to Example 24 Preparation of P52-P54 and P61: Employ the same process as described in Example 1 above to make samples P52-P54 and P61 of 5 kg each batch according to the carbon black composition, amount of carbon black (kg) and feeding rate (kg / h) disclosed in Table 1. Store the carbon black compositions in sealed aluminum containers for further use in the development of elastomeric compounds.
[0079] Comparative Examples 1 to 9 Preparation of P22, P28, P32, P35, P38, P41 and P51, P62, and P64: Employing the same process as described in Example 1 above, make 5 kg batches of samples P22, P28, P32, P35, P38, P41 and P51, P62, and P64 according to the carbon black composition, amount of carbon black (kg) and feeding rate (kg / h) disclosed in Table 1. Store the carbon black composition in a sealed aluminum container for further use in the development of elastomeric compounds.
[0080] Preparation of Elastomeric Compounds When making an elastomeric compound, a carbon black composition grade is prepared separately and then incorporated, along with one or more additives, into a rubber which, after vulcanization or curing, forms the elastomeric compound.
[0081] For purposes of this invention, raw rubber is defined as rubber, and vulcanized or cured rubber is defined as an elastomeric compound.
[0082] The carbon black of a given composition is adjusted to have an iodine adsorption value in the range of about 25 to 160 mg / g, preferably in the range of about 40 to 150 mg / g; 2 / g, preferably 35 to 140 m 2 A first carbon black, “Filler 1”, preferably having a nitrogen surface area (NSA) in the range of 70 to 140 ml / 100 g, more preferably an oil absorption number (OAN) in the range of 80 to 125 ml / 100 g, an iodine adsorption number in the range of 160 to 300 mg / g, an oil absorption number (OAN) in the range of 160 to 300 m 2 and at least one second carbon black having a nitrogen surface area in the range of 0.1 phr / 100 g and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, together with a filler 2, and compounded with a predetermined rubber, wherein the content of the carbon black composition in the elastomer compound is in the range of about 0.05 phr to 200 phr. Other formulation ingredients and the formulations of different rubber compounds are shown in Tables 2, 3, 4, 5 and 6.
[0083] Table 2: Rubber compound formulation (NR / BR) * TIFF2025024063000004.tif82170 * The amounts of rubber and rubber components are given in phr.
[0084] Table 2 (continued): Rubber compound formulations * TIFF2025024063000005.tif77170 * The amounts of rubber and rubber components are given in phr.
[0085] Masterbatches of each of the elastomer compounds listed in Table 2 were prepared by compounding the predetermined amounts of the carbon black composition and other additives, except for sulfur, CBS, and inhibitor (PVI), in a Banbury mixer for 4 minutes at a rotor speed of about 60 rpm to about 75 rpm. The carbon black mixed with the rubber and other compounding ingredients was further ground in a two-roll mill to form masterbatch sheets, which were maintained at room temperature for at least 24 hours.
[0086] After 24 hours, the masterbatch is mixed with the curing components (sulfur, CBS and inhibitors) in a Banbury mixer for 1.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compounds from the Banbury mixer are ground and homogenized in a two-roll mill to produce rubber sheets. The composition of the elastomer compound is shown in Table 2.
[0087] Example 26 Preparation of P23C: The following method is adopted to make an elastomeric compound "P23C". To prepare "P23C", 271.8 grams of a carbon black composition, "P23", containing 258.23 grams of one first carbon black, Filler 1, N339, and 13.59 grams of one second carbon black, Filler 2, EXP1, was used.
[0088] Preparation of Masterbatches About 302.02 grams of natural rubber (NR) is compounded in the Banbury mixer for about 15 seconds to about 20 seconds, followed by adding about 302.02 grams of butadiene rubber (BR) in the Banbury mixer and continuing the compounding process for another about 15 seconds to about 20 seconds. Then, about 135.9 grams of "P23" carbon black composition is added to the rubber in the Banbury mixer along with different additives such as 36.24 grams of ZnO, 0.30 grams of peptizer, 12.08 grams of stearic acid, 9.06 grams of TMQ, 12.08 grams of wax, 18.12 grams of 6PPD, and the total mass (total material) is compounded for about 20 seconds to about 30 seconds. The remaining about 135.9 grams of "P23" carbon black composition is added to the compounded mass (compounded material) in the Banbury mixer along with 36.24 grams of oil and compounding is continued until the end of 4 minutes from the start of the compounding process.
[0089] Blending in a Banbury mixer is carried out at a rotor speed of about 60 rpm to about 75 rpm, preferably 65 rpm to about 70 rpm. After the 4 minute blending period is completed, the masterbatch is collected from the Banbury mixer at a discharge temperature of the masterbatch compound of about 145°-155° C., ground on a two-roll mill to form a rubber sheet, and maintained at 250° C. for at least 24 hours.
[0090] Preparation of the Final Elastomer Compound A 835 gram masterbatch sample is compounded in a Banbury mix with 7.27 grams of sulfur, 6.56 grams of CBS, and 0.76 grams of PVI at a temperature range of about 90° C. to about 110° C. for about 2.5 minutes to about 1.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compound from the Banbury mixer was ground and homogenized in a two-roll mill.
[0091] Example 27 Preparation of P24C: The elastomeric compound "P24C" is made by employing the following method: 244.64 grams of one first carbon black, Filler 1, N339, and 27.18 grams of one second carbon black, Filler 2, EXP1 are mixed to obtain 271.8 grams of a carbon black composition, "P24." The masterbatch and final rubber compound of Example 27 are prepared by employing the same method as described in Example 26.
[0092] Example 28 Preparation of P25C: The following method is employed to make the elastomeric compound "P25C." 231.05 grams of one first carbon black, Filler 1, N339, and 40.77 grams of one second carbon black, Filler 2, EXP1 are mixed to obtain 271.8 grams of a carbon black composition, "P25." The masterbatch and final rubber compound of Example 28 are prepared by adopting the same method as described in Example 26.
[0093] Example 29 Preparation of P26C: The following method is employed to make the elastomeric compound "P26C." 271.8 grams of a carbon black composition, "P26," is obtained by mixing 217.46 grams of one first carbon black, Filler 1, N339, and 54.36 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 29 are prepared by adopting the same method as described in Example 26.
[0094] Example 30 Preparation of P27C: The following method is employed to make the elastomeric compound "P27C." 203.87 grams of one first carbon black, Filler 1, N339, and 67.96 grams of one second carbon black, Filler 2, EXP1 are mixed to obtain 271.8 grams of a carbon black composition, "P27." The masterbatch and final rubber compound of Example 30 are prepared by adopting the same method as described in Example 26.
[0095] Example 31 Preparation of P29C: The following method is employed to make the elastomeric compound "P29C." 271.8 grams of a carbon black composition, "P29," is obtained by mixing 190.27 grams of one first carbon black, Filler 1, N339, and 81.55 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 31 are prepared by adopting the same method as described in Example 26.
[0096] Example 32 Preparation of P30C: The following method is employed to make the elastomeric compound "P30C." 271.8 grams of a carbon black composition, "P30," is obtained by mixing 163.09 grams of one first carbon black, Filler 1, N339, and 108.73 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 32 are prepared by adopting the same method as described in Example 26.
[0097] Example 33 Preparation of P31C: The following method is employed to make the elastomeric compound "P31C." 271.8 grams of a carbon black composition, "P31," is obtained by mixing 135.91 grams of one first carbon black, Filler 1, N339, and 135.9 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 33 are prepared by adopting the same method as described in Example 26.
[0098] Example 34 Preparation of P36C: The following method is employed to make the elastomeric compound "P36C." 271.8 grams of a carbon black composition, "P36," is obtained by mixing 135.91 grams of one first carbon black, Filler 1, N134, and 135.9 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 34 are prepared by adopting the same method as described in Example 26.
[0099] Example 35 Preparation of P37C: The following method is employed to make the elastomeric compound "P37C." 217.46 grams of one first carbon black, Filler 1, N134, and 54.36 grams of one second carbon black, Filler 2, EXP1 are mixed to obtain 271.8 grams of a carbon black composition, "P37." The masterbatch and final rubber compound of Example 35 are prepared by adopting the same method as described in Example 26.
[0100] Example 36 Preparation of P39C: The following method is employed to make the elastomeric compound "P39C." 271.8 grams of a carbon black composition, "P39," is obtained by mixing 135.91 grams of one first carbon black, Filler 1, N660, and 135.9 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 36 are prepared by adopting the same method as described in Example 26.
[0101] Example 37 Preparation of P40C: The following method is employed to make the elastomeric compound "P40C." 271.8 grams of a carbon black composition, "P40," is obtained by mixing 217.46 grams of one first carbon black, Filler 1, N660, and 135.9 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 37 are prepared by adopting the same method as described in Example 26.
[0102] Comparative Example 10 Preparation of P38C: The following method is employed to make the elastomeric compound "P38C." 271.8 grams of a carbon black composition, "P38," is obtained by mixing 271.8 grams of one first carbon black, Filler 1, N660, and 0.0 grams of a second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Comparative Example 10 are prepared by adopting the same method as described in Example 26.
[0103] Comparative Example 11 Preparation of P28C: The following method is employed to make the elastomeric compound "P28C." 271.8 grams of one of the second carbon blacks, Filler 2, EXP1, and 0.0 grams of one of the first carbon blacks, Filler 1, N339 are mixed to obtain 271.8 grams of a carbon black composition, "P28." The masterbatch and final rubber compound of Example 11 are prepared by adopting the same method as described in Example 26.
[0104] Table 3: Rubber compound formulation (SBR / BR) * TIFF2025024063000006.tif67170 * The amounts of rubber and rubber components are given in phr.
[0105] Masterbatches of each elastomeric compound listed in Table 3 were prepared by compounding the predetermined amounts of the carbon black composition and other additives, except for sulfur, CBS, and inhibitor (PVI), in a Banbury mixer for 4 minutes at a rotor speed of about 60 rpm to about 75 rpm. The carbon black mixed with the rubber and other compounding ingredients was further ground in a two-roll mill to form masterbatch sheets, which were maintained at room temperature for at least 24 hours.
[0106] After 24 hours, the masterbatch is mixed with the curing components (sulfur, CBS and inhibitors) in a Banbury mixer for 1.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compounds from the Banbury mixer are ground and homogenized in a two-roll mill to produce rubber sheets. The composition of the elastomer compound is shown in Table 3.
[0107] Example 38 Preparation of P57C: The following method is adopted to make an elastomeric compound "P57C". To prepare "P57C", 312.1 grams of a carbon black composition, "P37", containing 249.7 grams of one first carbon black, Filler 1, N134, and 62.4 grams of one second carbon black, Filler 2, EXP1, was used.
[0108] Preparation of Masterbatches About 500 grams of styrene butadiene rubber (SBR) is compounded in a Banbury mixer for about 15 seconds to about 20 seconds, followed by adding about 156.0 grams of butadiene rubber (BR) into the Banbury mixer and continuing the compounding process for another about 15 seconds to about 20 seconds. Then, about 156.05 grams of "P37" carbon black composition is added to the rubber in the Banbury mixer along with different additives such as 15.6 grams of ZnO, 10.4 grams of stearic acid, 5.2 grams of TMQ, and the total mass (total material) is compounded for about 20 seconds to about 30 seconds. The remaining about 156.05 grams of "P37" carbon black composition is added to the compounded mass (compounded material) and compounding is continued until the end of 4 minutes from the start of the compounding process.
[0109] Blending in a Banbury mixer is carried out at a rotor speed of about 60 rpm to about 75 rpm, preferably 65 rpm to about 70 rpm.
[0110] After the 4 minute blending period is completed, the masterbatch is collected from the Banbury mixer at a discharge temperature of the masterbatch compound of about 145°-155° C., ground on a two-roll mill to form a rubber sheet, and maintained at 25° C. for at least 24 hours.
[0111] Preparation of the Final Elastomer Compound A 835 gram masterbatch sample is compounded in a Banbury mix with 6.5 grams of sulfur, 5.2 grams of CBS, and 0.9 grams of PVI at a temperature range of about 90° C. to about 110° C. for about 1.5 minutes to about 2.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compound from the Banbury mixer was ground and homogenized in a two-roll mill.
[0112] Example 39 Preparation of P58C: The elastomeric compound "P58C" is made by employing the following method: 218.5 grams of one first carbon black, Filler 1, N134, and 93.6 grams of one second carbon black, Filler 2, EXP1 are mixed to obtain 312.1 grams of a carbon black composition, "P58." The masterbatch and final rubber compound of Example 39 are prepared by employing the same method as described in Example 38.
[0113] Example 40 Preparation of P59C: The following method is employed to make the elastomeric compound "P59C." 312.1 grams of a carbon black composition, "P36," is obtained by mixing 156.0 grams of one first carbon black, Filler 1, N134, and 156.0 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 40 are prepared by adopting the same method as described in Example 38.
[0114] Comparative Example 12 Preparation of P60C: The following method is employed to make the elastomeric compound "P60C." 312.1 grams of a carbon black composition, "P28," is obtained by mixing 312.1 grams of a first carbon black, Filler 1, N134, and 312.1 grams of a second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Comparative Example 12 are prepared by adopting the same method as described in Example 38.
[0115] Table 4: Rubber compound formulation (IIR) * TIFF2025024063000007.tif66170 * The amounts of rubber and rubber components are given in phr.
[0116] Masterbatches of each elastomeric compound listed in Table 4 were prepared by compounding the desired amounts of the carbon black composition and other additives, except for sulfur, TMTD, and MBT, in a Banbury mixer for 4 minutes at a rotor speed of about 60 rpm to about 75 rpm. The carbon black mixed with the rubber and other compounding ingredients was further ground in a two-roll mill to form masterbatch sheets, which were maintained at room temperature for at least 24 hours.
[0117] After 24 hours, the masterbatch is mixed with the curing components (sulfur, TMTD and MBT) in a Banbury mixer for 2.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compounds from the Banbury mixer are ground and homogenized in a two-roll mill to produce rubber sheets. The composition of the elastomer compound is shown in Table 4.
[0118] Example 41 Preparation of P42C: The following method is adopted to make the elastomeric compound "P42C". To prepare "P42C", 348.3 grams of carbon black composition "42" containing 278.6 grams of one first carbon black, Filler 1, N774, and 69.7 grams of one second carbon black, Filler 2, EXP1 was used.
[0119] Preparation of Masterbatches About 300 grams of butyl (IIR) is compounded in the Banbury mixer for about 15 seconds to about 20 seconds, followed by adding about 197.5 grams of the remaining butyl rubber into the Banbury mixer and continuing the compounding process for another about 15 seconds to about 20 seconds. Then, about 174.15 grams of "P42" carbon black composition is added to the rubber in the Banbury mixer along with different additives such as 24.9 grams of ZnO, 5.0 grams of stearic acid, and the total mass (total material) is compounded for about 20 seconds to about 30 seconds. The remaining about 174.15 grams of "P37" carbon black composition is added to the compounded mass (compounded material) along with 124.4 grams of paraffinic oil and compounding is continued until the end of 4 minutes from the start of the compounding process.
[0120] Blending in a Banbury mixer is carried out at a rotor speed of about 60 rpm to about 75 rpm, preferably 65 rpm to about 70 rpm. After the 4 minute blending period is completed, the masterbatch is collected from the Banbury mixer at a discharge temperature of the masterbatch compound of about 145°-155° C., ground on a two-roll mill to form a rubber sheet, and maintained at 25° C. for at least 24 hours.
[0121] Preparation of the Final Elastomer Compound A 835 gram masterbatch sample is compounded in a Banbury mix with 8.3 grams of sulfur, 2.1 grams of MBT, and 6.2 grams of TMTD at a temperature range of about 90° C. to about 110° C. for about 1.5 minutes to about 2.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compound from the Banbury mixer was ground and homogenized in a two-roll mill.
[0122] Example 42 Preparation of P43C: The elastomeric compound "P43C" is made by employing the following method: 244.0 grams of one first carbon black, Filler 1, N774, and 104.6 grams of one second carbon black, Filler 2, EXP1 are mixed to obtain 348.3 grams of a carbon black composition, "P43." The masterbatch and final rubber compound of Example 42 are prepared by employing the same method as described in Example 41.
[0123] Example 43 Preparation of P44C: The following method is employed to make the elastomeric compound "P44C." 348.3 grams of a carbon black composition, "P44," is obtained by mixing 174.15 grams of one first carbon black, Filler 1, N774, and 174.15 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 43 are prepared by adopting the same method as described in Example 41.
[0124] Example 44 Preparation of P63C: The following method is employed to make the elastomeric compound "P63C." 348.3 grams of a carbon black composition, "P63," is obtained by mixing 174.15 grams of one first carbon black, Filler 1, N774, and 174.15 grams of one second carbon black, Filler 2, EXP3. The masterbatch and final rubber compound of Example 44 are prepared by adopting the same method as described in Example 41.
[0125] Comparative Example 13 Preparation of P45C: The following method is employed to make the elastomeric compound "P45C." 348.3 grams of a carbon black composition, "P28," is obtained by mixing 348.3 grams of a first carbon black, Filler 1, N774, and 348.3 grams of a second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Comparative Example 13 are prepared by adopting the same method as described in Example 41.
[0126] Comparative Example 14 Preparation of P64C: The following method is employed to make the elastomeric compound "P64C." 348.3 grams of a carbon black composition, "P64," is obtained by blending 300 grams of a first carbon black, Filler 1 N774, and 348.3 grams of a second carbon black, Filler 2, EXP3. The masterbatch and final rubber compound of Comparative Example 14 are prepared by adopting the same method as described in Example 41.
[0127] Table 5: Rubber compound formulation (NBR)* TIFF2025024063000008.tif69170 * The amounts of rubber and rubber components are given in phr.
[0128] Masterbatches of each of the elastomer compounds listed in Table 5 were prepared by compounding the prescribed amounts of the carbon black composition and other additives, except for sulfur, TMT, and MBTS, in a Banbury mixer for 4 minutes at a rotor speed of about 60 rpm to about 75 rpm. The carbon black mixed with the rubber and other compounding ingredients was further ground in a two-roll mill to form masterbatch sheets, which were maintained at room temperature for at least 24 hours.
[0129] After 24 hours, the masterbatch is mixed with the curing components (sulfur, TMT and MBTS) in a Banbury mixer for 2.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compounds from the Banbury mixer are ground and homogenized in a two-roll mill to produce rubber sheets. The composition of the elastomer compound is shown in Table 5.
[0130] Example 45 Preparation of P47C: The following method is adopted to make an elastomeric compound "P47C". To prepare "P47C", 300.3 grams of a carbon black composition, "P40", containing 240.2 grams of one first carbon black, Filler 1, N660, and 60.1 grams of one second carbon black, Filler 2, EXP1, was used.
[0131] Preparation of Masterbatches About 300 grams of nitrile butadiene rubber (NBR) is compounded in a Banbury mixer for about 15 seconds to about 20 seconds, followed by adding about 300.6 grams of the remaining nitrile butadiene rubber into the Banbury mixer and continuing the compounding process for another about 15 seconds to about 20 seconds. Then, about 150.3 grams of "P40" carbon black composition is added to the rubber in the Banbury mixer along with different additives such as 30.0 grams of ZnO, 9.0 grams of stearic acid, 6.0 grams of TDQ, 6.0 grams of paraffin wax, and the total mass (total material) is compounded for about 20 seconds to about 30 seconds. The remaining about 150.0 grams of "P40" carbon black composition is added to the compounded mass (compounded material) along with 48.0 grams of aromatic oil and compounding is continued until the end of 4 minutes from the start of the compounding process. Blending in a Banbury mixer is carried out at a rotor speed of about 60 rpm to about 75 rpm, preferably 65 rpm to about 70 rpm. After the 4 minute blending period is completed, the masterbatch is collected from the Banbury mixer at a discharge temperature of the masterbatch compound of about 145°-155° C., ground on a two-roll mill to form a rubber sheet, and maintained at 25° C. for at least 24 hours.
[0132] Preparation of the Final Elastomer Compound A 830.1 gram masterbatch sample is compounded in a Banbury mix with 9.97 grams of sulfur, 4.99 grams of MBTS, and 4.9 grams of TMT at a temperature range of about 90° C. to about 110° C. for about 1.5 minutes to about 2.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compound from the Banbury mixer was ground and homogenized in a two-roll mill.
[0133] Example 46 Preparation of P48C: The following method is employed to make the elastomeric compound "P48C": 300.3 grams of a carbon black composition, "P48," is obtained by mixing 180.2 grams of one first carbon black, Filler 1, N660, and 120.1 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 46 are prepared by employing the same method as described in Example 45.
[0134] Example 47 Preparation of P49C: The following method is employed to make the elastomeric compound "P49C." 300.3 grams of a carbon black composition, "P39," is obtained by mixing 150.15 grams of one first carbon black, Filler 1, N660, and 150.15 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 47 are prepared by adopting the same method as described in Example 45.
[0135] Comparative Example 15 Preparation of P50C: The following method is employed to make the elastomeric compound "P50C." 300.3 grams of a carbon black composition, "P28," is obtained by mixing 300.3 grams of a first carbon black, Filler 1, N660, and 300.3 grams of a second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Comparative Example 15 are prepared by adopting the same method as described in Example 45.
[0136] Table 6: Rubber compound formulation (EPDM) * TIFF2025024063000009.tif84170 * The amounts of rubber and rubber components are given in phr.
[0137] Masterbatches of each of the elastomer compounds listed in Table 6 were prepared by compounding the desired amounts of the carbon black composition and other additives, except for sulfur, TMT, MBT, and ZDBC, in a Banbury mixer for 4 minutes at a rotor speed of about 60 rpm to about 75 rpm. The carbon black mixed with the rubber and other compounding ingredients was further ground in a two-roll mill to form masterbatch sheets, which were maintained at room temperature for at least 24 hours.
[0138] After 24 hours, the masterbatch is mixed with the curing components (sulfur, TMT and MBT and ZDBC) in a Banbury mixer for 2.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compounds from the Banbury mixer are ground and homogenized in a two-roll mill to produce rubber sheets. The composition of the elastomer compound is shown in Table 6.
[0139] Example 48 Preparation of P52C: The following method is adopted to make an elastomeric compound "P52C". To prepare "P52C", 441.2 grams of a carbon black composition, "P52", containing 352.9 grams of one first carbon black, Filler 1, N550, and 88.2 grams of one second carbon black, Filler 2, EXP1, was used.
[0140] Preparation of Masterbatches About 100 grams of ethylene propylene diene monomer (EPDM) is compounded in a Banbury mixer for about 15 seconds to about 20 seconds, followed by adding about 241.2 grams of "P52 carbon black composition" along with different additives such as 14.7 grams of ZnO, 5.9 grams of stearic acid, 2.9 grams of paraffin wax, 5.9 grams of TDQ to the rubber in the Banbury mixer and compounding the entire mass (total material) for about 20 seconds to about 30 seconds, after which 194.1 grams of the remaining EPDM rubber is added into the Banbury mixer and compounding process continues for another about 15 seconds to about 20 seconds. The remaining about 200 grams of "P52" carbon black composition is added to the compounded mass (compounded material) along with 235.3 grams of paraffinic oil and compounding continues until 4 minutes have elapsed since the start of the compounding process.
[0141] Blending in a Banbury mixer is carried out at a rotor speed of about 60 rpm to about 75 rpm, preferably 65 rpm to about 70 rpm.
[0142] After the 4 minute blending period is completed, the masterbatch is collected from the Banbury mixer at a discharge temperature of the masterbatch compound of about 145°-155° C., ground on a two-roll mill to form a rubber sheet, and maintained at 25° C. for at least 24 hours.
[0143] Preparation of the Final Elastomer Compound A 838.6 gram masterbatch sample is compounded in a Banbury mix with 3.70 grams of sulfur, 3.70 grams of MBT, 1.97 grams of TMT, and 1.97 grams of ZDBC at a temperature range of about 90° C. to about 110° C. for about 1.5 minutes to about 2.5 minutes at a rotor speed of about 30 rpm to about 40 rpm. The compound from the Banbury mixer was ground and homogenized in a two-roll mill.
[0144] Example 49 Preparation of P53C: The elastomeric compound "P53C" is made by employing the following method: 441.2 grams of a carbon black composition, "P53," is obtained by mixing 308.8 grams of one first carbon black, Filler 1, N550, and 132.4 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 49 are prepared by employing the same method as described in Example 48.
[0145] Example 50 Preparation of P54C: The following method is employed to make the elastomeric compound "P54C." 441.2 grams of a carbon black composition, "P54," is obtained by mixing 220.6 grams of one first carbon black, Filler 1, N550, and 220.6 grams of one second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Example 50 are prepared by adopting the same method as described in Example 48.
[0146] Example 51 Preparation of P61C: The following method is employed to make the elastomeric compound "P61C." 441.2 grams of a carbon black composition, "P61," is obtained by mixing 220.6 grams of one first carbon black, Filler 1, N550, and 220.6 grams of one second carbon black, Filler 2, EXP2. The masterbatch and final rubber compound of Example 51 are prepared by adopting the same method as described in Example 48.
[0147] Comparative Example 16 Preparation of P55C: The following method is employed to make the elastomeric compound "P55C." 441.2 grams of a carbon black composition, "P28," is obtained by mixing 441.2 grams of a first carbon black, Filler 1 N550, and 441.2 grams of a second carbon black, Filler 2, EXP1. The masterbatch and final rubber compound of Comparative Example 16 are prepared by adopting the same method as described in Example 48.
[0148] Comparative Example 17 Preparation of P62C: The following method is employed to make the elastomeric compound "P62C." 441.2 grams of a carbon black composition, "P62," is obtained by mixing 441.2 grams of a first carbon black, Filler 1 N550, and 441.2 grams of a second carbon black, Filler 2, EXP2. The masterbatch and final rubber compound of Comparative Example 17 are prepared by adopting the same method as described in Example 48.
[0149] It is to be understood that both the foregoing general description and the following detailed description are exemplary and are intended to provide further explanation of the invention as claimed. The advances made by the present invention will be discussed in further detail in connection with the following non-limiting illustrative description.
[0150] Colloidal Properties of Carbon Black Composition Grades Colloidal properties of the carbon black composition including one first carbon black, Filler 1, and one second carbon black, Filler 2, such as iodine adsorption number (mg / g), nitrogen surface area (NSA, m), measured by adopting ASTM standards, ASTM D1510, ASTM D6556, ASTM D2414, ASTM D3493 and ASTM D3265. 2 / g), statistical surface area (STSA, m 2 / g), oil absorption number (OAN, ml / 100g), compressed oil absorption number (COAN, ml / 100g), and coloring strength units are shown in Tables 7, 8 and 9. The variation in color intensity of carbon black compositions containing one first carbon black, Filler 1, and different amounts of one second carbon black, Filler 2, is shown in FIG.
[0151] Table 7: Colloidal properties of carbon black compositions (based on N339) TIFF2025024063000010.tif73170
[0152] Table 8: Colloidal properties of carbon black compositions (based on N234, N134 and N660) TIFF2025024063000011.tif73170
[0153] Table 9: Colloidal properties of carbon black compositions (based on N774 and N550) TIFF2025024063000012.tif77170
[0154] Color Properties of Carbon Black Compositions The color properties of carbon black or carbon black compositions are measured by ASTM D3265 in tinting strength units, which are a measure of the ability of carbon black to hide the whiteness value of a white pigment. A higher tinting strength value of the carbon black indicates a higher intensity of the black color of the carbon black. Iodine adsorption value in the range of about 25 to 160 mg / g, 20 m 2 / g~150m 2 A first carbon black having a nitrogen surface area (NSA) in the range of 70 ml / 100 g to 140 ml / 100 g, an oil absorption number (OAN) in the range of 70 ml / 100 g to 140 ml / 100 g, and an iodine adsorption number in the range of 160 mg / g to 300 mg / g, and an oil absorption number (OAN) in the range of 160 mg / g to 300 mg / g. 2 / g~300m 2 The tinting strength of the carbon black composition containing one second carbon black having a nitrogen surface area (NSA) in the range of 100 ml / 100 g to 120 ml / 100 g, and filler 2, exhibits higher values, and the carbon black composition contains different amounts of increasing filler 2.
[0155] Iodine adsorption value in the range of 60mg / g to 100mg / g, 70m 2 / g~100m 2For carbon black compositions comprising one first carbon black as filler 1 having a nitrogen surface area (NSA) in the range of 100 mg / g to 130 ml / 100 g and an oil absorption number (OAN) in the range of 60 ml / 100 g to 130 ml / 100 g, and one second carbon black, filler 2, having an iodine adsorption number in the range of 200 mg / g to 270 mg / g and an oil absorption number (OAN) in the range of 50 ml / 100 g to 110 ml / 100 g, the tinting strength is improved by about 20% for carbon black composition P31, which consists of 50 wt% filler 1 and 50 wt% filler 2, compared to P22, which contains 100 wt% filler 1. See Table 7 and Figure 1.
[0156] Iodine adsorption value in the range of 115mg / g~160mg / g, 110m 2 / g~150m 2 For carbon black compositions including one first carbon black, Filler 1, having an iodine adsorption number in the range of 200 mg / g to 270 mg / g, and an oil absorption number (OAN) in the range of 110 ml / 100 g to 140 ml / 100 g, and one second carbon black, Filler 2, having an iodine adsorption number in the range of 200 mg / g to 270 mg / g, and an oil absorption number (OAN) in the range of 50 ml / 100 g to 110 ml / 100 g, the tinting strength is improved by about 5.5 and 4.2% for carbon black compositions P36 and P33, which contain 50 wt% Filler 1 and 50 wt% Filler 2, compared to P35 and P32, which contain 100 wt% Filler 1. See Table 8 and Figure 1.
[0157] Iodine adsorption value in the range of 25mg / g to 50mg / g, 25m 2 / g~45m 2In the case of a carbon black composition including one first carbon black as filler 1 having a nitrogen surface area (NSA) in the range of 1 / g and an oil absorption number (OAN) in the range of 60 ml / 100g to 130 ml / 100g, and one second carbon black as filler 2 having an iodine adsorption number in the range of 200 mg / g to 270 mg / g, and an oil absorption number (OAN) in the range of 50 ml / 100g to 110 ml / 100g, Color strength is improved by about 65, 80.7, 82.7, and 129.2% for carbon black compositions P39, P44, P63, and P61, respectively, which contain 50% by weight of Filler 1 and 50% by weight of Filler 2, compared to P38 (N660), which contains 100% by weight of Filler 1, P41 (N774), which contains 100% by weight of Filler 1, and P51 (N550), which contains 100% by weight of Filler 1. See Tables 8 and 9 and FIG. 1.
[0158] Aggregate Size Distribution (ASD) of Carbon Black Compositions The present invention provides an iodine adsorption value in the range of about 25 to 160 mg / g, preferably in the range of about 40 to 150 mg / g; 2 / g, preferably 35 to 140 m 2 At least one first carbon black having a nitrogen surface area (NSA) in the range of 70 to 140 ml / 100 g, more preferably an oil absorption number (OAN) in the range of 80 to 125 ml / 100 g, a filler 1 and an iodine adsorption number in the range of 160 to 300 mg / g, more preferably an oil absorption number (OAN) in the range of 160 to 300 mg / g, 2 / g~300m 2 The carbon black composition includes at least one second carbon black having a nitrogen surface area (NSA) in the range of 100 to 120 ml / 100 g and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, and a filler 2, and the weight of the second carbon black and filler 2 in the carbon black composition varies between 0.5% by weight and 99.5% by weight.
[0159] The present invention describes a carbon black composition grade comprising at least two different carbon blacks, a first carbon black, Filler 1, and a second carbon black, Filler 2, that have a unimodal aggregate size distribution (ASD), i.e., only one peak across the aggregate size distribution of the carbon black composition. The carbon black composition grade of the present invention has an iodine adsorption value of Filler 1 in the range of about 55 mg / g to 145 mg / g, preferably in the range of about 65 mg / g to 135 mg / g; 2 / g~140m 2 / g range, preferably 70m 2 / g~130m 2 / g; and an Oil Adsorption Number (OAN) in the range of about 70ml / 100g to 140ml / 100g, preferably in the range of 80ml / 100g to 130ml / 100g, showing a unimodal aggregate size distribution. See Figures 2 and 3.
[0160] The present invention describes a carbon black composition comprising at least two different carbon blacks, a first carbon black, Filler 1, and a second carbon black, Filler 2, having a bimodal aggregate size distribution (ASD), i.e., two peaks throughout the aggregate size distribution of the carbon black composition. In the carbon black composition of the present invention, the filler 1 has an iodine adsorption value in the range of about 25 to 55 mg / g; 2 / g; and an oil absorption number (OAN) in the range of about 60-130 ml / 100 g, which shows a bimodal aggregate size distribution, i.e., at least two peaks in the overall aggregate size distribution. See FIG. 4. Mass-weighted average aggregate size D W and the number-weighted average aggregate size D N The ratio of EXP1 to D indicates the uniformity of the aggregate size distribution. Higher values of the ratio indicate non-uniformity, while relatively lower values of the ratio approaching 1 indicate greater uniformity of the blend aggregate size distribution. In the carbon black composition of the present invention, as the content of EXP1 gradually increases, D W / D N The ratio increases.
[0161] For carbon black composition P22 (N339:EXP1=100:00), the ratio value is 1.40, and for P24 (N339:EXP1=90:10), P25 (N339:EXP1=85:15), P26 (N339:EXP1=80:20), P29 (N339:EXP1=70:30), P30 (N339:EXP1=60:40), P31 (N339:EXP1=50:50), P28 (N339:EXP1=00:100), the ratio values are 1.67, 1.66, 1.72, 1.91, 1.94, 1.98, 1.6, respectively. See Table 10. For carbon black composition P35 (N134:EXP1=100:00), the ratio value is 1.40, while for P37 (N134:EXP1=80:20) and P36 (N134:EXP1=50:50), the ratio values are 1.42 and 1.52, respectively. See Table 10.
[0162] D of carbon black composition containing N134 as filler 1 W / D N Ratios of N339 and N134 show better uniformity with Filler 2 when compared to N339 at comparable weight ratios. Carbon black compositions containing N339 (P22, P23, P24, P25, P26 and P29) and N134 (P35, P37 and P36) as Filler 1 show unimodal aggregate size distributions as observed from Figures 2 and 3. D of carbon black composition containing N660 as filler 1 W / D NThe ratio of filler 2 shows heterogeneity when compared to N339 at comparable weight ratios. Carbon black compositions containing N339 (P22, P23, P24, P25, P26 and P29) and N134 (P35, P37 and P36) as filler 1 show a unimodal aggregate size distribution as observed from Figures 2 and 3, whereas for carbon black compositions P40 and P39 containing 20 wt. % (curve 3, Figure 4) and 50 wt. % (curve 4, Figure 4) of filler 2 in filler 1, N660, a bimodal distribution of aggregate sizes is observed.
[0163] The width of the aggregate size distribution is expressed by the full width at half maximum (FWHM) and is denoted as ΔD50. ΔD50 represents the width of the mass distribution measured at the half-maximum point of the mode in the differential volume distribution curve of the aggregate size distribution of carbon black. The relative fractional magnitude of the width is calculated by dividing ΔD50 by the mode diameter D Mode It is derived by dividing by ΔD50 / D Mode This ratio is a measure of the broadness of the aggregate size distribution curve without extrapolating smaller and larger aggregate sizes.
[0164] For carbon black compositions, P22 (N339:EXP1 = 100:00), P23 (N339:EXP1 = 95:05), P24 (N339:EXP1 = 90:10), P25 (N339:EXP1 = 85:15), P26 (N339:EXP1 = 80:20), P29 (N339:EXP1 = 70:30), P30 (N339:EXP1 = 60:40), and P31 (N339:EXP1 = 50:50), ΔD50 and ΔD50 / D Mode The values of ΔD50 and ΔD50 / D increase gradually with increasing weight percent of Filler 2, EXP1, in Filler 1, N339, from 63 nm and 0.625 (P22) to 88 nm and 0.93. See Table 10, Figures 5 and 6. The present invention provides ΔD50 and ΔD50 / D Mode The carbon black compositions exhibit a broader aggregate size distribution characterized by:
[0165] For carbon black compositions P35 (N134:EXP1 = 100:00), P37 (N134:EXP1 = 80:20), and P36 (N134:EXP1 = 50:50), ΔD50 and ΔD50 / D Mode The values of increase gradually from 55 nm and 0.695 (P35) to 58 nm and 0.88 with increasing weight percent of filler 2, EXP1, in filler 1, N134. See Table 10, Figures 7 and 8.
[0166] However, for the carbon black compositions P38 (N660:EXP1=100:00), P40 (N660:EXP1=80:20), and P39 (N660:EXP1=50:50), ΔD50 and ΔD50 / D Mode The values of Filler 1, Filler 2 in N660, and EXP1 did not change significantly with increasing weight percentage, and P38 (ΔD50-156 nm, ΔD50 / D Mode 0.831), P40(ΔD50-157nm, ΔD50 / D Mode 0.86) and P39 (ΔD50-153 nm, ΔD50 / D Mode 0.856). See Table 10, Figures 9 and 10.
[0167] Table 10: Aggregate Size Distribution (ASD) of Carbon Black Compositions TIFF2025024063000013.tif56170
[0168] Curing of Elastomeric Compounds The cure characteristics of the elastomer compounds were evaluated by oscillating disc rheometer (ODR) at 145°C for 30 minutes for NR / BR elastomer compounds, 160°C for 30 minutes for SBR / BR elastomer compounds, 170°C for 30 minutes for IIR elastomer compounds, 160°C for 30 minutes for NBR elastomer compounds, and 170°C for 30 minutes for EPDM elastomer compounds.
[0169] Rubber compound molding The rubber compounds for preparing the elastomer compounds described in Tables 2, 3, 4, 5 and 6 are molded and cured at temperatures up to 175°C, up to 160°C, about 145°C to about 175°C or any other predetermined temperature therebetween, up to about 250 kg / cm 2 More preferably, under a pressure of about 200 kg / cm 2 The compression press was conducted under a pressure of 0.05 g for up to 60 minutes, up to 45 minutes, from about 10 minutes to about 40 minutes, or any other predetermined time therebetween.
[0170] Properties of Elastomer Compounds Comparison of variance Carbon black is used as a filler in vulcanizable rubber compositions of matter used to make tire components and other rubber articles, and the degree of dispersion of carbon black in these compositions ultimately affects the properties of the tire or other rubber article. Carbon black is typically added to these rubber compositions during compounding, a process that involves mixing of rubber, fillers, and other compound ingredients. Processing aids are added during mixing to improve carbon black dispersion [continuation of U.S. patent application Ser. No. 10 / 022,108, filed Dec. 13, 2001].
[0171] Filler dispersibility is mainly influenced by the interactions between the agglomerates and / or aggregates, in other words the force / energy required to separate the two bodies. In the case of carbon black, these interactions are mainly due to van der Waals forces, which are very low compared to the hydrogen bonds present between silica bodies. Furthermore, the pelletization process has a large effect on dispersibility, and any action that results in a higher compaction of the filler increases the interactions between the filler bodies and therefore reduces its dispersibility. In addition to the surface energy of the filler, which is of primary importance, dispersibility can also be influenced by the morphological properties of the filler. Dispersion is greatly influenced by the surface area of the filler, the higher the surface area of carbon black, the lower the dispersibility. This result is probably due to the fact that high surface areas usually have smaller aggregates, which generate more interactions with their neighbors in the dry state. The filler structure also has a positive effect on dispersibility, the higher the structure, the better the dispersibility. This result is well established and can be likened to the fact that more "open" aggregate structures generate a lower number of contacts with their neighbors in the dry state. [James E. Mark, Burak Erman, Frederick R. Eirich, Science and Technology of RUBBER (Academic Press is an imprint of Elsevier, Third Edition, 2005)].
[0172] The dispersion properties of the carbon black elastomer compounds were evaluated according to standard ISO 11345 (dispersion (%), X, average agglomerate size) and the dispersion properties of the elastomer compounds relative to the comparative samples are shown in Table 11. The disperGRADER Alpha View is an advanced reflected light microscope designed to measure filler dispersion in elastomeric compounds. The Dispersion (%) value indicates the % level of dispersion of the carbon black (or filler) in the elastomeric compound. The X value is a built-in instrument assessment of carbon black agglomeration in an elastomeric compound relative to an image reference scan. It is a measure of filler distribution, with higher X values indicating better distribution. The average agglomerate size (μm) in the disperGRADER is the average of all visible agglomerate diameters of the carbon black in the elastomeric compound.
[0173] Table 11: Dispersion (%), X and average agglomerate size data for elastomer compounds TIFF2025024063000014.tif149170
[0174] Dispersion properties of elastomer compounds Dispersion (%) represents the % level of dispersion of the carbon black (or filler) in the elastomeric compound. The most dispersed compound has a Dispersion (%) value of -100, and the least dispersed compound has a Dispersion (%) value of -0; the X value represents the assessment of the filler distribution in the elastomeric compound. X-10 indicates the highest filler distribution, and X-0 indicates the lowest filler distribution; Average Agglomerate Size represents the average agglomerate diameter of all counted agglomerates of carbon black in the elastomeric compound. A smaller average agglomerate size indicates better dispersion and vice versa. The carbon black compositions were prepared by mixing different levels of one first carbon black, Filler 1, and one second carbon black, Filler 2, P26C (N339:EXP1-80:20), P30C (N339:EXP1-60:40), P31C (N339:EXP1-50:50) and P28C (EXP1 100, Comparative Example; P57C (N134:EXP1-80:20), P59C (N134:EXP1-50:50), P60C (N134:EXP1-00:100, Comparative Example); P42C (N774:EXP1-80:20), P44C (N774:EXP1-50:50), P45C (N774:EXP1-00:100, Comparative Example); P47C (N660:EXP1-80:20), P49C (N660:EXP1-50:50), P50C (660:EXP1-00:100, Comparative Example) The dispersibility of the elastomeric compounds containing P54C (N550:EXP1-50:50), P55C (N550:EXP1-00:100 comparative sample) shows a gradual increase in the value of dispersion (%), X and a decrease in the value of average agglomerate size, which indicates that the dispersibility of carbon black in the elastomeric compounds is improved with increasing content of one second carbon black, filler 1, in the carbon black composition, for P28C, P60C, P45C, P50C and P55C, respectively.
[0175] Mechanical Properties of Elastomer Compounds The present invention relates to an elastomeric compound of natural rubber, synthetic rubber or a selected blend thereof, comprising a carbon black composition having a synergistically improved distribution of aggregate sizes ΔD50 to provide improved mechanical properties of the elastomeric compound, such as tear strength and break growth, the elastomeric compound having synergistically improved dispersibility of the carbon black composition comprising at least two different carbon blacks; an iodine adsorption number in the range of about 25-160 mg / g, preferably in the range of about 40-150 mg / g; a nitrogen surface area (NSA) in the range of 20-150 m2 / g, preferably in the range of 35-140 m2 / g; an NSA in the range of 70-140 ml / 100 g, more preferably in the range of 50-60 ml / 100 g; It is prepared by mixing at least one first carbon black, filler 1, preferably having an oil absorption number (OAN) of 80-125 ml / 100 g, with at least one second carbon black, filler 2, preferably having an iodine adsorption number in the range of 160-300 mg / g, a nitrogen surface area (NSA) in the range of 160-300 m2 / g, an oil absorption number (OAN) in the range of 50-120 ml / 100 g, which varies between 0.5% and 99.5% by weight, preferably between 2.5% and 97.5% by weight in the carbon black composition, and the content of the carbon black composition in the elastomeric compound is in the range of about 0.05 phr to 200 phr.
[0176] The mechanical properties of the elastomeric compounds were evaluated according to standards ASTM D412 (tensile strength, elongation at break, modulus), ASTM D624 (tear strength), ASTM D430 (growth at break). The evolution of the mechanical properties of the elastomeric compounds is shown in Tables 12, 13, 14, 15 and 16, as well as in Figures 11, 12, 13 and 14. For each elastomer compound, the mechanical property values of the comparative samples (P22C, P35C, P38C, P56C, P41C, P46C, P51C - data not shown) were converted to 100 and the mechanical property values of the experimental elastomer compounds were compared relative to the comparative samples as 100. See Tables 12, 13, 14, 15 and 16. Thus, the mechanical property values of the experimental samples are compared to the comparative samples considering the mechanical property values as 100. The values in brackets are absolute values. The values in brackets are absolute values in units MPa, MPa, %, N / mm, mm for tensile strength, modulus at 300%, elongation at break, tear strength, break growth, respectively.
[0177] Table 12: Changes in mechanical properties of elastomer compound (N339 / EXP-1) TIFF2025024063000015.tif60170
[0178] Table 12 (continued): Changes in mechanical properties of elastomeric compounds (NR / BR), (N134 / B219) and (N660 / B219) TIFF2025024063000016.tif41170
[0179] Table 13: Changes in mechanical properties of elastomer compounds (butyl rubber) (N774 / B219) and (N774 / B361) TIFF2025024063000017.tif52170All samples failed before 20KC in Table 13.
[0180] Table 14: Change in mechanical properties of elastomer compound (SBR / BR) (N134 / B219) TIFF2025024063000018.tif40170
[0181] Table 15: Changes in mechanical properties of elastomer compound (NBR) (N660 / B219) TIFF2025024063000019.tif45170
[0182] Table 16: Change in mechanical properties of elastomer compounds (EPDM) (N550 / B219 or N115) TIFF2025024063000020.tif33170
[0183] The mechanical properties of the elastomeric compounds such as tensile strength, modulus, elongation at break, tear strength, break growth, etc. are listed in Tables 12, 13, 14, 15 and 16. For plotting Figures 11, 12, 13 and 14, the raw data of mechanical and color properties (in brackets) have been customized (other data in cells).
[0184] tear strength Elastomeric compounds P23C, P24C, P25C, P26C, P27C, P29C, P30C, P31C (Table 12) containing carbon black composition, N339 as filler 1, and EXP1 as filler 2 show higher tear strength when incorporated in NR / BR when the carbon black composition contains increased amounts of filler 2 (Table 12). For the elastomeric compound P31C, which contains a carbon black composition of 50 wt. % of one first carbon black, Filler 1, N339, and 50 wt. % of one second carbon black, Filler 2, EXP1 (Table 12), the carbon black composition exhibits higher tear strength when it contains a higher amount of Filler 2 in the carbon black composition (Table 12 (continued)).
[0185] The elastomeric compounds containing carbon black composition, N134 as Filler 1, and EXP1 as Filler 2, P37C, P36C (Table 12 (continued)) show higher tear strength when the carbon black composition contains higher amount of Filler 2 in the carbon black composition (Table 12 (continued)).
[0186] The elastomeric compounds with carbon black composition, N660 as Filler 1, and EXP1 as Filler 2, P40C, P39C (Table 12 (continued)) show higher tear strength when the carbon black composition contains higher amount of Filler 2 (Table 12). The elastomeric compounds P42C, P43C, P44C and P45C, P63C (Table 13) containing carbon black composition, N774 as filler 1, and EXP1 and EXP3 as filler 2 show higher tear strength when the carbon black composition contains higher amount of filler 2 in the carbon black composition (Table 13). Elastomeric compounds P57C, P58C, P59C and P60C containing carbon black composition, N134 as filler 1 and EXP1 as filler 2 (Table 14) show higher tear strength when incorporated in SBR / BR as the amount of filler 2 in the carbon black composition increases (Table 14)
[0187] The elastomeric compounds P47C, P48C, P49C and P50C (Table 15) containing carbon black composition, N660 as filler 1 and EXP2 as filler 2 show higher tear strength when the carbon black composition contains higher amount of filler 2 in the carbon black composition (Table 15).
[0188] The elastomeric compounds P52C, P53C, P54C and P55C, P61C containing carbon black compositions, N550 as filler 1, and EXP1 and EXP2 as filler 2 (Table 16) show higher tear strength when the carbon black composition contains higher amount of filler 2 in the carbon black composition (Table 16). [Raw data for tear strength (in brackets) have been customized for plotting Figure 11 (other data in cells).]
[0189] cutting growth The break growth of elastomeric compounds including carbon black compositions, N339, N134, N660 and N774 as filler 1, and EXP1, EXP3 as filler 2 (Tables 12-15) show at least an improvement in break growth below 10KC and 20KC when the carbon black composition contains up to about 30% by weight of filler 2 in the carbon black composition, more preferably up to 50% by weight of filler 2, preferably about 50% by weight of filler 2 in the carbon black composition (Tables 12-15). [Raw data (in brackets) for break growth improvement properties are customized in the tables (other data in cells)]
[0190] Elongation at break Elastomeric compounds containing carbon black compositions, N339, N134, N660 and N774 as Filler 1, and EXP1, EXP2, EXP3 as Filler 2 (Tables 12-16) show improved elongation at break when the carbon black composition contains up to about 50 wt. % of Filler 2 in the carbon black composition of Filler 1 (Tables 12-16). [Raw data for elongation at break (in brackets) are customized in the tables (other data in cells)]
[0191] Tensile strength Elastomeric compounds containing carbon black compositions N339, N134, N660 and N774 as Filler 1 and EXP1, EXP2, EXP3 as Filler 2 (Tables 12-16) show improved tensile strength when the carbon black composition contains higher amount of Filler 2 in the carbon black composition, 50 wt% of Filler 2 in the carbon black composition of Filler 1 (as shown in Tables 12-16).
[0192] Color Properties of Elastomeric Compounds The present invention relates to improved color properties of elastomeric compounds, e.g., L *To provide an improved method for treating elastomeric compounds of natural rubber, synthetic rubber or selected blends thereof comprising a carbon black composition, the carbon black composition has at least two different carbon blacks, an iodine adsorption number in the range of about 25-160 mg / g, preferably about 40-150 mg / g; a nitrogen surface area (NSA) in the range of 20-150 m2 / g, preferably about 35-140 m2 / g; an oil absorption number (OAN) in the range of 70-140 ml / 100 g, more preferably about 80-125 ml / 100 g, compared to a first carbon black comprising an elastomeric compound of natural rubber, synthetic rubber or selected blends thereof comprising a carbon black composition, the carbon black composition has at least two different carbon blacks, an iodine adsorption number in the range of about 25-160 mg / g, preferably about 40-150 mg / g; a nitrogen surface area (NSA) in the range of 20-150 m2 / g, preferably about 35-140 m2 / g; an oil absorption number (OAN) in the range of 70-140 ml / 100 g, more preferably about 80-125 ml / 100 g. The carbon black composition is prepared by mixing at least one first carbon black, filler 1 having an iodine adsorption number (OAN) in the range of 70-140 ml / 100 g, more preferably 80-125 ml / 100 g, with at least one second carbon black, filler 2 having an iodine adsorption number in the range of 160-300 mg / g, a nitrogen surface area (NSA) in the range of 160-300 m2 / g, and an oil absorption number (OAN) in the range of 50-120 ml / 100 g, the weight of the second carbon black, filler 2 in the carbon black composition varies between 0.5 wt% and 99.5 wt%, preferably between 2.5 wt% and 95 wt%, and the content of the carbon black composition in the elastomeric compound is in the range of about 0.05 phr to 200 phr. Comparison samples P22C, P35C, P38C, P56C, P41C, P46C, P51C L * Convert the value to 100 and calculate the L of the experimental elastomer compound. * Values are compared relative to the control sample as 100 (Table 17). Values in brackets are absolute L * value.
[0193] Table 17: L of elastomer compounds * Value Change TIFF2025024063000021.tif108170
[0194] Elastomer compound L * value Different levels of one first carbon black, filler 1, one second carbon black, filler 2, P23C (N339:EXP1-95:05), P24C (N339:EXP1-90:10), P25C (N339:EXP1-85:15), P26C (N339:EXP1-80:20), P27C (N339:EXP1-75:25), P29C (N339:EXP1-70:30), P30C (N339:EXP1-60:40), P31C (N339:EXP1-50:50) and P28C (EXP1 L of elastomer compositions containing P39C (N660:B219); P59C (N134:EXP1-50:50); P44C (N774:EXP1-50:50), P63C (N774:EXP3-50:50); P51C (N550:EXP1-100:00, comparative example), P54C (N550:EXP1-50:50), and P61C (N550:EXP2-50:50). * The value is L * 1 shows a gradual decrease in the value of 1,2,3,4,5,6, which indicates an improvement in the color density of the elastomeric compound with increasing content of one second carbon black, Filler 2, in the carbon black composition.
[0195] Thus, according to the present invention, there is provided a first carbon black having an iodine adsorption number in the range of about 25 mg / g to 160 mg / g, a nitrogen surface area (NSA) in the range of 20 m2 / g to 150 m2 / g, and an oil absorption number (OAN) in the range of 70 ml / 100 g to 140 ml / 100 g, a filler 1, and a carbon black having an iodine adsorption number in the range of 160 mg / g to 300 mg / g, an oil absorption number (OA) in the range of 50 ml / 100 g to 120 ml / 100 g ... Selective blending of two carbon blacks that synergistically enhance the distribution of aggregate size width ΔD50 of a second carbon black, Filler 2 having a composition of 0.5 wt% to 99.5 wt% N, when incorporated at 0.05 phr to 200 phr of an elastomeric compound, has surprisingly improved L with concomitant improvement in mechanical properties such as tear strength, break growth, tensile strength, and elongation at break. *It is demonstrated that the value is shown.
Claims
1. 1. A carbon black composition comprising a high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, and processability for making elastomeric compounds, the carbon black composition comprises a synergistic combination of a first carbon black having an iodine adsorption number in the range of 30.5 to 146.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m / g, an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g, and a second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, the high surface area carbon black comprising said first carbon black and said second carbon black selectively varying between 0.5% and 50% by weight; the carbon black composition provides a synergistically improved breadth ΔD50 of aggregate size distribution of the carbon black composition for each of the first carbon black and the high surface area carbon black; the value of the synergistically improved breadth of aggregate size distribution, ΔD50, of the carbon black composition is improved when the amount of the second carbon black in the carbon black composition varies between 0.5 wt.% and 50 wt.%; The carbon black compositions incorporating the high surface area carbon blacks have desirable processability and dispersibility in elastomeric compounds ranging from 87.71 to 99.87%, and improved mechanical properties including, selectively, tear strength, elongation at break, or tensile strength of the elastomeric compounds. Carbon black composition.
2. the synergistically enhanced width of the aggregate size distribution, ΔD50, as expressed by the full width at half maximum, is in the range of 50 nm to 160 nm; the ratio of the mass weighted average aggregate size Dw to the number weighted average aggregate size DN of the carbon black composition is in the range of 1.4 to 4.02; 2. The carbon black composition of claim 1.
3. the magnitude of the curve spread of the distribution, defined by the ratio of the width to the mode of the distribution, ΔD50 / Dmode, is in the range of 0.63 to 0.9; 3. The carbon black composition according to claim 1 or 2.
4. wherein the carbon black composition has an aggregate size distribution that is either a unimodal aggregate size distribution or a bimodal aggregate size distribution depending on the selective combination of the first carbon black and the second carbon black.
4. The carbon black composition according to claim 1 .
5. The carbon black composition comprises: As a combination of weight percent of any of N339, N134, N660, N774, and N550 as the first carbon black and any of EXP1, EXP2, and EXP3 as the second carbon black, N339:EXP1=95% by weight:05% by weight, N339:EXP1=90% by weight:10% by weight, N339:EXP1=85% by weight:15% by weight, N339:EXP1=80% by weight:20% by weight, N339:EXP1=75% by weight:25% by weight, N339:EXP1=70% by weight:30% by weight, N339:EXP1=60% by weight:40% by weight, N339:EXP1=50% by weight:50% by weight, N134:EXP1=50% by weight:50% by weight, N134:EXP1=80% by weight:20% by weight, N134:EXP1=70% by weight:30% by weight, N660:EXP1=50% by weight:50% by weight, N660:EXP1=80% by weight:20% by weight, N660:EXP1=70% by weight:30% by weight, N774:EXP1=80% by weight:20% by weight, N774:EXP1=70% by weight:30% by weight, N774:EXP1=50% by weight:50% by weight, N774:EXP3=50% by weight:50% by weight, N550:EXP1=80% by weight:20% by weight, N550:EXP1=70% by weight:30% by weight, N550:EXP1=50% by weight:50% by weight, N550:EXP2=50% by weight:50% by weight, Including, EXP1 is B219 having an iodine adsorption number of 256.75 mg / g, a nitrogen surface area of 262.98 m2 / g, and an oil absorption number of 94.8 ml / 100 g; The EXP3 is B361 having an iodine adsorption number of 292.0 mg / g, a nitrogen surface area of 294.0 m2 / g, and an oil absorption number of 70.0 ml / 100 g; The EXP2 is N115 having an iodine adsorption number of 162 mg / g, a nitrogen surface area of 156 m2 / g, and an oil absorption number of 115 ml / 100 g; 5. The carbon black composition according to claim 1 .
6. The carbon black composition comprises: P23 having 95% by weight of N339 and 0.5% by weight of B219; P24 having 90% by weight of N339 and 10% by weight of B219; P25 having 85% by weight of N339 and 15% by weight of B219; P26 having 80% by weight of N339 and 20% by weight of B219; P29 having 70% by weight of N339 and 30% by weight of B219; P30 having 60% by weight of N339 and 40% by weight of B219; P31 having 50% by weight of N339 and 50% by weight of B219; Either The N339 has an iodine adsorption number of 89.0 mg / g, a nitrogen surface area of 86.2 m2 / g, and an oil absorption number of 119.8 ml / 100 g; the width value and the magnitude of the spread increase from 63 nm and 0.625 to 88 nm and 0.93 with increasing weight percent of the B219 as the second carbon black relative to the N339 as the first carbon black in the carbon black composition; 6. The carbon black composition according to claim 1 .
7. The carbon black composition comprises: P37 having 80% by weight of N134 and 20% by weight of B219; P36 having 50% by weight of N339 and 50% by weight of B219; Either The N134 has an iodine adsorption number in the range of 146.75.0 mg / g, a nitrogen surface area of 139.9 m2 / g, and an oil absorption number of 121.4 ml / 100 g; the width value and the magnitude of the spread increase from 55 nm and 0.695 to 58 nm and 0.88 with increasing weight percent of the B219 as the second carbon black relative to the N134 as the first carbon black in the carbon black composition; 6. The carbon black composition according to claim 1 .
8. The carbon black composition comprises: P40 having 80% by weight of said N660 and 20% by weight of said B219; P39 having 50% by weight of said N660 and 50% by weight of said B219; Either The N660 has an iodine adsorption value of 37.5 mg / g, a nitrogen surface area of 35.1 m2 / g, and an oil absorption value of 91.2 ml / 100 g; the width value and the magnitude of the spread do not change with increasing weight percent of B219 as the second carbon black relative to N660 as the first carbon black in the carbon black composition; Or, The carbon black composition comprises: P42 having 80% by weight of N774 and 20% by weight of B219; P43 having 70% by weight of N774 and 30% by weight of B219; P44 having 50% by weight N774 and 50% by weight B219; Either The N774 has an iodine adsorption value of 30.5 mg / g, a nitrogen surface area of 31.5 m2 / g, and an oil absorption value of 73.0 ml / 100 g; the width value and the magnitude of the spread increase from 186 nm and 1.038 to 192 nm and 1.162 with an increase in the weight percent of the B219 as the second carbon black relative to the N774 as the first carbon black in the carbon black composition; Or, The carbon black composition comprises: P52 having 80% by weight of N550 and 20% by weight of B219; P53 having 70% by weight of N550 and 30% by weight of B219; P54 having 50% by weight of N550 and 50% by weight of B219; P61 having 50% by weight of N550 and 50% by weight of N115; Either The N550 has an iodine adsorption value of 43.2 mg / g and a nitrogen surface area of 36.09 m2 / g. , 119.
6. ml / 100 g oil absorption number; the width value and the magnitude of the spread change from 161 nm and 0.865 to 155 nm and 1.122 with increasing weight percent of the B219 as the second carbon black relative to the N550 as the first carbon black in the carbon black composition; 6. The carbon black composition according to claim 1 .
9. 9. An elastomeric compound incorporating the carbon black composition according to claim 1 , comprising: (I) A carbon black composition comprising a high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, the carbon black composition comprising: (a) an iodine adsorption number in the range of 30.5 to 145.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m2 / g, (b) at least one first carbon black having an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g; and (b) at least a second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g; a carbon black composition, wherein the high surface area carbon black in the carbon black composition is selectively varied between 0.5 wt.% and 50 wt.%, the carbon black composition providing a synergistically enhanced width ΔD50 of aggregate size distribution of the carbon black composition for each of the first carbon black and the high surface area carbon black, the value of the synergistically enhanced width ΔD50 of aggregate size distribution of the carbon black composition being improved when the second carbon black in the carbon black composition is varied between 0.5 wt.% and 50 wt.%; (II) elastomeric rubber compounds, including NR / BR, SBR / BR, NBR, EPDM, and IIR; including a synergistic combination of The carbon black composition, which comprises a high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, has desirable processability and dispersibility in an elastomeric compound in the range of 87.71 to 99.87%, and improved mechanical properties, selectively including tear strength, elongation at break, or tensile strength of the elastomeric compound. Elastomeric compounds.
10. the proportion of said carbon black composition in said rubber compound is within the range of 0.5 phr to 150 phr (per 100 weight percent rubber); improved aesthetic and color properties, including L* values, in the range of 15.38 to 5.05; The tear strength is within the range of 33 N / mm to 198 N / mm, The elongation at break is 240% to 750%. The elastomer compound of claim 9.
11. the carbon black composition comprises N339 as the first carbon black and B219 as the second carbon black; the B219 is 50 wt. % of the carbon black composition, which is 45 phr (per 100 wt. rubber) in total; The elastomer compound achieves a tear strength in the range of 145 N / mm to 155 N / mm. The elastomer compound of claim 9.
12. the carbon black composition comprises N660 as the first carbon black and B219 as the second carbon black; the B219 is 50 wt. % of the carbon black composition, which is 45 phr (per 100 wt. rubber) in total; The elastomer compound achieves a tear strength in the range of 95 N / mm to 110 N / mm. The elastomer compound of claim 9.
13. the carbon black composition comprises N134 as the first carbon black and B219 as the second carbon black; the B219 is 50 wt. % of the carbon black composition, which is 45 phr (per 100 wt. rubber) in total; The elastomer compound achieves a tear strength in the range of 195 N / mm to 210 N / mm. The elastomer compound of claim 9.
14. the carbon black composition comprises N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the carbon black composition; Or, the carbon black composition comprises N774 as the first carbon black and B361 as the second carbon black; the B361 is 50% by weight of the carbon black composition; The elastomer compound exhibits a tear strength of 45 N / mm to 55 N / mm. The elastomer compound of claim 9.
15. the carbon black composition comprises N134 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomeric compound of claim 9, wherein the elastomeric compound exhibits a tear strength of from 100 N / mm to 115 N / mm.
16. The carbon black composition comprises N660 as the first carbon black and and B219 as a second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a tear strength of 70 N / mm to 85 N / mm. The elastomer compound of claim 9.
17. The carbon black composition comprises N550 as the first carbon black and and B219 as a second carbon black; the B219 is 50% by weight of the total carbon black composition; Or, the carbon black composition comprises N550 as the first carbon black and N115 as the second carbon black; said N115 being 50% by weight of the total carbon black composition; The elastomer compound exhibits a tear strength of 40 N / mm to 55 N / mm. The elastomer compound of claim 9.
18. the carbon black composition comprises N339 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 5.5 to 3.
5. The elastomer compound of claim 9.
19. the carbon black composition comprises N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 10.5 to 9.
5. The elastomer compound of claim 9.
20. the carbon black composition comprises N134 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 10.5 to 9.
5. The elastomer compound of claim 9.
21. the carbon black composition comprises N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 7.8 to 6.
8. The elastomer compound of claim 9.
22. the carbon black composition comprises N660 as the first carbon black and B361 as the second carbon black; The B361 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 7.5 to 6.
5. The elastomer compound of claim 9.
23. the carbon black composition comprises N550 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 6.5 to 5.
5. The elastomer compound of claim 9.
24. the carbon black composition comprising N550 as the first carbon black and N115 as the second carbon black; said N115 being 50% by weight of the total carbon black composition; The elastomer compound exhibits an L* value of 8.5 to 7.
5. The elastomer compound of claim 9.
25. the carbon black composition comprises N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a break growth of 10.0 mm to 9.0 mm for 10KC and 15.0 mm to 14.0 mm for 20KC when loaded with 45 phr total carbon black. The elastomer compound of claim 9.
26. the carbon black composition comprises N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a break growth of 13.0 mm to 12.0 mm at 10 KC when loaded with 70 phr total carbon black. The elastomer compound of claim 9.
27. the carbon black composition comprises N134 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a break growth of 9.0 mm to 8.0 mm for 10KC and 13.0 mm to 12.0 mm for 20KC when loaded with 60 phr total carbon black. The elastomer compound of claim 9.
28. the carbon black composition comprises N339 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprises N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprises N550 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprises N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits an elongation at break of 240% to 750%. The elastomer compound of claim 9.
29. the carbon black composition comprises N339 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprises N660 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprises N550 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; or the carbon black composition comprises N774 as the first carbon black and B219 as the second carbon black; the B219 is 50% by weight of the total carbon black composition; The elastomer compound exhibits a tensile strength of 6.0 MPa to 28.0 MPa. The elastomer compound of claim 9.
30. 1. A process for producing a carbon black composition, comprising the steps of: comprising a high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, and processability for making elastomeric compounds; said including comprising: providing a synergistic combination of: (a) a first carbon black having an iodine adsorption number in the range of 30.5 to 145.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m2 / g, an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g; and (b) a second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g; the high surface area carbon black in the carbon black composition selectively varies between 0.5% and 50% by weight; the carbon black composition provides a synergistically improved breadth ΔD50 of aggregate size distribution of the carbon black composition for each of the first carbon black and the high surface area carbon black; the value of the synergistically improved breadth of aggregate size distribution, ΔD50, of the carbon black composition is improved when the amount of the second carbon black in the carbon black composition varies between 0.5 wt.% and 50 wt.%; The carbon black compositions incorporating the high surface area carbon black have desirable processability and dispersibility in elastomeric compounds in the range of 87.71 to 99.87%, and improved mechanical properties including, selectively, tear strength, elongation at break, or tensile strength of the elastomeric compounds. method.
31. 1. A process for producing an elastomeric compound incorporating a carbon black composition, comprising: comprising a high surface area carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160.0 to 294.0 m2 / g, an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g, and processability to make an elastomeric compound; I) providing a carbon black composition in combination with said high surface area carbon blacks, said carbon blacks comprising: (a) at least one first carbon black having an iodine adsorption number in the range of 30.5 to 146.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m2 / g, and an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g; and (b) at least a second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g; the high surface area carbon black in the carbon black composition selectively varies between 0.5% and 50% by weight; the carbon black composition provides a synergistically enhanced width ΔD50 of aggregate size distribution of the carbon black composition for each of the first carbon black and the high surface area carbon black, the value of the synergistically enhanced width ΔD50 of aggregate size distribution of the carbon black composition being improved when the amount of the second carbon black in the carbon black composition is varied between 0.5 wt.% and 50 wt.%; II) incorporating the carbon black composition into an elastomeric rubber according to a conventional process for producing an elastomeric compound; having desirable processability and dispersibility in the range of 87.71 to 99.87% in an elastomeric compound, and improved mechanical properties, optionally including tear strength, elongation at break, or tensile strength of the elastomeric compound; method.
32. a carbon black composition comprising: (a) at least one first carbon black having an iodine adsorption number in the range of 30.5 to 146.75 mg / g, a nitrogen surface area (NSA) in the range of 31.5 to 139.9 m2 / g, and an oil absorption number (OAN) in the range of 73 to 121.4 ml / 100 g; and (b) at least one second carbon black having an iodine adsorption number in the range of 162.0 to 292.0 mg / g, a nitrogen surface area (NSA) in the range of 160 to 294.0 m2 / g, and an oil absorption number (OAN) in the range of 50 to 120 ml / 100 g; and a rubber compound; the second carbon black in the carbon black composition ranges from 0% to 50% by weight; the carbon black composition has a width of aggregate size distribution, expressed as a full width at half maximum, said width increasing with increasing weight percentage of the second carbon black in the carbon black composition within said range; the width is in the range of 63 nm to 88 nm when the first carbon black is N339, in the range of 55 nm to 58 nm when the first carbon black is N134, and in the range of 153 nm to 157 nm when the first carbon black is N660; the ratio of the mass weighted average aggregate size DW to the number weighted average aggregate size DN of the carbon black composition is in the range of 1.4 to 2 when the first carbon black is N339, in the range of 1.4 to 1.52 when the first carbon black is N134, and in the range of 1.57 to 4.02 when the first carbon black is N660; the magnitude of the spread of the curve of the distribution, defined by the ratio of the width to the mode of the distribution, is in the range of 0.63 to 0.9 when the first carbon black is N339, in the range of 0.77 to 0.88 when the first carbon black is N134, and in the range of 0.83 to 0.88 when the first carbon black is N660; Elastomeric compounds.
33. the rubber compound comprises at least one of NR / BR, SBR / BR, NBR, EPDM, and IIR; The elastomeric compound has an improved dispersion of carbon black in the elastomeric compound within the range of 87.71 to 99.87%.
33. The elastomeric compound of claim 32.
34. an L* value in the range of 15.38 to 5.05; Tear strength in the range of 33 N / mm to 198 N / mm; Cutting growth in the range of 26.38 mm to 8.78 mm; Tensile strength in the range of 5.57 MPa to 25.06 MPa; Elongation at break in the range of 208% to 732%; Selectively having aesthetic, color and mechanical properties including 33. An elastomeric compound according to claim 31 or 32.
Citation Information
Patent Citations
Carbon black
JP1995500631A
Elastomer composition with improved appearance
JP2002531661A
Tire with tread of rubber composition containing diverse carbon blacks
US20050159535A1